Accelerated climate-induced risks of nitrogen-loss from agricultural catchments: Empirical modelling of extreme weather events using climate change scenarios - G. Ezzati; P. Mellander; J. Ortega; B. Fan; C. Murphy (Water Research, 2027)

Spatio-temporal dynamics of Lagos flooding: comparative multi-parameter analysis of 2011 and 2021 events - O. O. Oyegbile; A. Chan; P. Anwar; A. Ali Mohamed; L. Huang; L. Li; Murphy Lai (Bulletin of Atmospheric Science and Technology, 2026)
This study examines changes in flooding characteristics in Lagos, Nigeria, through comparative analysis of major flooding events in July 2011 and July 2021. Satellite data from NASA’s IMERG and MODIS platforms were used to analyse precipitation patterns, aerosol concentrations, and land surface temperatures through spatial autocorrelation and regression analysis. The comparison reveals substantial changes in flood characteristics over this decade of rapid urban development. Maximum flood intensity decreased from 1,053 mm to 760 mm, while flood-prone areas shifted from western urban to eastern coastal regions. Surface temperatures reduced from 43 °C to 39 °C in established urban areas. Notably, the aerosol-precipitation relationship changed from negative spatial correlation (ρ = -0.21) in 2011 to positive correlation (ρ = 0.47) in 2021, suggesting modified atmospheric processes. Spatial clustering patterns weakened (Moran’s I: 0.92 to 0.86), indicating changing spatial organization of flood parameters. Built-up areas increased by 37% with impervious surface coverage expanding from 48 to 68%, while flood duration increased by 5 h despite lower peak intensities. These observed changes occurred alongside regional climate modifications, including a 1 °C increase in sea surface temperatures and 8% rise in atmospheric moisture content. The findings suggest that flood vulnerability in rapidly growing coastal cities may evolve substantially over decadal timescales, requiring adaptive management strategies that can respond to changing urban-climate interactions. While these observations are specific to Lagos, they provide insights that may be relevant for other rapidly developing coastal megacities experiencing similar urbanization and climate pressures.

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Mangrove genera influence bed shear stress and coastal protection ecosystem services - Alice J. Twomey; Dylan Cowley; Simon J. Murphy; David P. Callaghan; Marc Koh; Neil Saintilan; Catherine E. Lovelock (Water Research, 2026)

“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Is there a threshold for use-dependent plasticity? A study of repeated motor skill training in the human lower limbs - Alex Woodhead; Ryan Norbury; Jessica Hill; Colm P. Murphy; Jamie S. North; Dawson Kidgell; Jamie Tallent (European Journal of Applied Physiology, 2026)

Estimation of cercospora leaf spot disease severity in table beets from UAS multispectral images - Mohammad S. Saif; Robert Chancia; Pratibha Sharma; Sean P. Murphy; Sarah Pethybridge; Jan van Aardt (Computers and Electronics in Agriculture, 2026)

Buffelgrass (Pennisetum ciliare) invasion is associated with reduced plant diversity and changes in carbon storage in the Sonoran Desert - R. Chelsea Nagy; Emily J. Fusco; Adam L. Mahood; Dylan P. Murphy; Jennifer K. Balch; Kimberly Franklin; Bethany A. Bradley (Journal of Arid Environments, 2026)

Impact of high-pressure processing on technological properties of hybrid plant-beef patties - Zuo Song; Joseph P. Kerry; Mohammad Hassan Kamani; Ahmed Rady; Eoin G. Murphy; Ruth M. Hamill (Innovative Food Science & Emerging Technologies, 2026)

Marine Isotope Stage 4 glaciation in northern England, UK: Evidence from Victoria Cave, North Yorkshire - Tom C. Lord; Peter Wilson; Joyce Lundberg; Adrian P. Palmer; Matt W. Telfer; Rhiannon E. Stevens; Phillip J. Murphy; Mark Lewis (Journal of Quaternary Science, 2026)
Victoria Cave, north Yorkshire, England, contains a long sequence of Pleistocene clastic sediments and calcite flowstones. Earlier work, using U–Th dating, established that the flowstone units formed in interglacial stages corresponding to Marine Isotope Stages (MIS) 13, 11, 9, 7 and 5. The intervening laminated sediments were therefore assigned to glacial stages (MIS 12, 10, 6 and 2) and regarded as rhythmites that settled from ponded glacial meltwater in the cave. Victoria Cave is a rare instance of cave rhythmites that formed over a number of glacial–interglacial cycles. The macro‐ and micromorphologies of the rhythmites support the above interpretation, and the mineralogy demonstrates that the sediments probably derive from rock types within the local area. An OSL age of 66 ± 8.4 ka from the uppermost unit of the rhythmites and two 14 C ages of 46.1–54.9 cal. ka BP and 48.9–>55.0 cal. ka BP, for horse and reindeer, respectively, from the overlying Bone‐bearing Cave Earth provide a new chronology for these Late Pleistocene sediments. Together, these results indicate that the youngest rhythmites in Victoria Cave formed during MIS 4 and not MIS 2 as previously assumed. This provides strong support for more widespread glaciation in northern England in MIS 4 (~71–59 ka) than has previously been recognised. The MIS 4 rhythmites represent the most tightly constrained cave rhythmites in Britain and the first terrestrial‐based evidence from this area for glaciation at that time.

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Marine algae growth and carbon capture augmentation by antioxidant nanozymes - Supreetha Sivaraj; Hye-In Kim; Su-Ji Jeon; Arnav Deshpande; Conor P. Murphy; Sandeep Sharma; Robert E. Jinkerson; Lieve M.L. Laurens; Juan Pablo Giraldo (Algal Research, 2026)

Assessing nitrogen balance and use efficiency across multiple scales on pasture based dairy farms and implications for nitrogen management and policy - Philip M. Murphy; Paul N.C. Murphy; David P. Wall (Agricultural Systems, 2026)

The Integration of Fire Ecology and Freshwater Ecosystems in North America: Knowledge Gaps and Research Needs - Morgan L. Piczak; Ava J. A. Sergio; Caliyena R. Brown; Waverley S. Birch; Rebecca L. Flitcroft; Meg A. Krawchuk; Colin P. R. McCarter; Jonathan W. Moore; Brendan P. Murphy; Brooke E. Penaluna; Prabha A. Rupasinghe; Victoria Steblaj; et al. (Global Change Biology, 2026)
Wildfires, unplanned fires that start and spread under the influence of weather and fuel composition, are increasing in frequency, duration, and severity across North America. While wildfires are one component of wildland fire, a broader natural process in many ecosystems, their changing behavior poses growing ecological and management challenges. Although wildfire is widely recognized as an important disturbance, empirical research quantifying its impacts on freshwater ecosystems remains limited and fragmented. As a result, our understanding of how wildfire affects imperiled freshwater systems remains underdeveloped. The objective of this review was to synthesize the existing empirical literature and identify key knowledge gaps to guide future research on wildfire–freshwater interactions across both biotic and abiotic components. At the biological scale, uncertainties remain around species‐ and community‐level responses (e.g., direct and indirect effects on biota). Freshwater habitat dimensions should also be the focus of further research, including alterations to physical structure (e.g., vegetation) and physicochemical conditions (e.g., temperature). From a management perspective, critical questions relate to fire‐informed restoration (e.g., specialized techniques, role of managed burns) and strategies for enhancing ecosystem resilience (e.g., identifying relevant indicators, links to watershed health). Understanding how land‐use change (e.g., forestry) and climate change interact to influence wildfire regimes and generate cumulative effects across landscapes is also essential in this new wildfire reality. To advance research and practice, we recommend comprehensive monitoring, standardization of methods and indicators, recognition of the role of cultural and prescribed burns, meaningful knowledge co‐production, and bridging the gap between scientific knowledge and management action.

A Coast-to-Coast Assessment of Cumulative Impacts and Protection Potential in Canadian Marine Conservation Networks - Grace E. P. Murphy; Selina Agbayani; Jocelyn C. Nelson; Emily M. Rubidge; Ryan R. E. Stanley; Cathryn C. Murray; Noreen E. Kelly (Environmental Management, 2026)
The effectiveness of marine conservation networks depends on their ability to manage and safeguard against the many overlapping human activities and stressors influencing marine ecosystems. Cumulative impact mapping (CIM) combines information on the intensity and location of stressors with the spatial extent and vulnerability of marine habitats to generate a single, relative cumulative impact (CI) score. Despite its potential benefits to inform management and conservation efforts, CIM is not commonly incorporated into conservation network planning. Here, we combine published CIMs from the Canadian Atlantic and Pacific bioregions with existing marine conservation areas (MCAs) to compare impacts inside each MCA against regional impacts. We then conduct a scenario analysis to quantify potential reduction in cumulative impacts in two bioregion’s proposed marine conservation networks by modeling the removal of prohibited activities (bottom contact fishing, dredging, disposal at sea) in alignment with the Canadian Marine Protection Standard. Both regions exhibited similar distributions in current CI scores, with approximately half of MCAs scoring significantly above the regional mean, and the other half below. The scenario analysis predicted a 7% mean decrease (range 0–36%) in cumulative impacts across the Scotian Shelf and 2% mean decrease (range 0–17%) across the Northern Shelf networks. We identified 17 MCAs in the Scotian Shelf and 8 in the Northern Shelf as having high protection potential, which can be a valuable decision support tool for conservation planners. We discuss how CIM can be operationalized for conservation network planning and management.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Incorporating fire severity mapping into fuel accumulation curves - Christopher E. Gordon; Luke Collins; Meaghan Jenkins; Brett P. Murphy; Trung H. Nguyen; Owen F. Price; Liubov Volkova; Christopher J. Weston; Rachael H. Nolan (Science of The Total Environment, 2026)

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Lagged streamflow depletion due to pumping-induced stream drying: Incorporation into analytical streamflow depletion estimation methods - Sam Zipper; Ian Gambill; Monty Schmitt; Claire Kouba; Leland Scantlebury; Thomas Harter; Nicholas P. Murphy (Journal of Hydrology, 2026)

Diameter, height, and volume as macroscopic predictors of photocarcinogenesis in UV-induced SKH1 papules - Mehdi Boostani; Alaina F. Carman; Erin C. Tracy; Sean P. Murphy; Rhea Carmel Glen Rodrigues; Katalin Ferenczi; Gillian Weston; Olayemi Sokumbi; Gyorgy Paragh; Wendy J. Huss (Journal of Photochemistry and Photobiology B: Biology, 2026)

Sensory profile and drivers of liking of grass-fed and total mixed ration butters - Lauren McGuinness; Mark Timlin; Sean A. Hogan; Tom F. O'Callaghan; John P. Murphy; Deirdre Hennessy; Michael O'Donovan; Ellen Fitzpatrick; Kieran McCarthy; E. Dolores O'Riordan; Andre Brodkorb; Emma L. Feeney (Food Quality and Preference, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Acute UV response of early erythema and late edema in SKH1 mice - Szabolcs Bozsányi; Rhea Carmel Glen Rodrigues; Ruby Acquah; Erin C. Tracy; Sean P. Murphy; Jocelyn Tracy; Li Yan; Mehdi Boostani; Hamid-Reza Rezvani; Wendy J. Huss; Gyorgy Paragh (Journal of Photochemistry and Photobiology B: Biology, 2026)

Advancing table beet root yield estimation via unmanned aerial systems (UAS) multi-modal sensing - Mohammad S. Saif; Robert Chancia; Sean P. Murphy; Sarah Pethybridge; Jan van Aardt (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

The potential for unwanted genetic rescue in invasive fallow deer populations - Lauren C. White; Erin Hill; Eliane D. McCarthy; Andrew J. Bengsen; Sebastien Comte; Sandie Czarka; David M. Forsyth; Catherine E. Grueber; Jake Haddad; Jordan O. Hampton; Michelle Hanslow; Scott Jennings; et al. (Biological Invasions, 2026)

Soil property controls on plasticiser, antioxidant and UV absorber additive degradation across a global soil gradient - Michaela K. Reay; Martine Graf; Maddy Murphy; Charlie Monkley; Perrine J. Florent; Benjamin I. Collins; Nguyen Van Hien; Tran Minh Tien; Andreia Neves Fernandes; Tapan Adhikari; Samantha Viljoen; Mona Tolba; et al. (Environmental Science and Pollution Research, 2025)
Additives in agricultural plastics can leach into the surrounding soil during use or improper disposal. Their subsequent degradation rates directly regulate whether they persist and accumulate to levels with ecotoxicological effects or are rendered benign. However, which soil properties primarily regulate the degradation of additives remains unclear (e.g. soil carbon, pH, available nutrients, microbial biomass and community structure). We assessed the degradation of the common plastic additives with different functionalities (DEHP (di(2-ethylhexyl) phthalate; plasticiser), 2-hydroxy-4-n-octyloxybenzophenone (benzophenone-12; BP12; UV stabiliser) and AO168 (tris(2,4-di- tert -butylphenyl) phosphite; antioxidant)) in soils under controlled moisture and temperature conditions over 21 days across contrasting agricultural soils from six countries across a global transect (Australia, Brazil, Egypt, India, Vietnam and the UK). DEHP followed zero-order degradation kinetics, with negligible degradation in soils with low microbial biomass. BP12 degraded fastest via first-order degradation kinetics via ether cleavage and hydroxyl loss. The degradation of DEHP and BP12 was correlated with soil microbial biomass and nitrate concentration. BP12 degradation products detected included benzophenone and benzoic acid. DEHP is degraded via β-oxidation of alkyl groups to dibutyl phthalate and diethyl phthalate and through ester hydrolysis to phthalic acid. AO168 degraded via abiotic oxidation and phosphate ester hydrolysis to 2,4-di- tert -butyl-phenol, and degradation was not well correlated with any measured soil variable. Overall, these results show that the components of additive mixtures leached into soils will degrade at different rates due to varying mechanisms and controls exerted by the soil microbial biomass. Plastic additives have differing potentials to persist in agricultural soils globally, with some likely to accumulate to levels that may impact soil function and pose an ecotoxicological threat to soil biota.

The 10/20/30 planting rule aligns with traditional plant diversity metrics across spatial scales - Michael R. Freiburger; Colleen Murphy-Dunning; Danica A. Doroski; P. Mark Ashton; Jacob D.J. Peters (Urban Forestry & Urban Greening, 2025)

A baseline assessment of the occurrence, characterization, source, and risk impact of petroleum-related hydrocarbons in sediments along the southeast shoreline of Vancouver Island and Southern Gulf Islands in British Columbia, Canada - Zeyu Yang; Keval Shah; Claire Courtemanche; Sonia Laforest; Bruce P. Hollebone; Antoine Rolland; Pascal Hebert; Patrick Lambert; Michael Goldthorp; Yuan Yao; Michael J.J. Murphy; Chun Yang; et al. (Regional Studies in Marine Science, 2025)

Pairing OpenET remotely sensed evapotranspiration with streamflow data to assess the effectiveness of irrigation curtailment for aquatic conservation - J. Eli Asarian; Bronwen Stanford; Nicholas P. Murphy; Michael M. Pollock (Journal of Hydrology, 2025)

Ensuring consistent data quality for environmental rating ecolabels with representative secondary datasets - Maëlys Courtat; P. James Joyce; Sarah Sim; Mohamad Kaddoura; Jhuma Sadhukhan; Richard Murphy (The International Journal of Life Cycle Assessment, 2025)
Purpose Environmental rating ecolabels (ERE) are developing rapidly across Europe, intending to guide sustainable purchasing choices through performance ratings derived from life cycle assessment (LCA). Integrating robust data quality methods in the LCA modelling stage is essential for accurate and comparable ratings, but challenging as ERE must be feasible to generate with reasonable effort for broad adoption. The use of secondary life cycle inventory (LCI) datasets, alongside actual product information such as bills of materials, is inevitable. However, the selection process for secondary LCI datasets and its implications for environmental ratings have yet to be investigated. Methods We examine the context-dependent suitability of secondary LCI datasets (aka their representativeness), hypothesising that differing levels of representativeness could lead to differences in product ratings. In a case study involving 94 laundry detergent products, we investigate how different secondary dataset choices influence the resulting aggregated LCA results (single scores), relative product rankings, and environmental ratings. Four distinct data scenarios are defined, in which the production of 19 key ingredients is represented through datasets of varying representativeness (from most specific to most generic). Results Over 60% of the products studied obtained a different rating under at least one of the three lower representativeness (more generic) data scenarios explored as compared with the rating obtained when the highest representativeness (most specific) data scenario was used. Lower representativeness scenarios also led to wider distributions of product single scores, with scenarios which utilised LCI data representing the function of ingredients (e.g. alkalinity source) or generic LCI data (e.g. organic chemicals) showing the most significant deviations from the distributions under the specific data scenario. This highlights the importance of having clearly defined, consistent data quality management approaches for the LCA stage of ERE. Conclusions Product information (e.g. formulation and packaging specifications) from primary sources should be combined with representative LCI datasets from third party databases to obtain reliable product ratings. We demonstrate that the representativeness of secondary datasets can be evaluated through three contextual indicators of data quality (technological, geographical, and temporal representativeness) to help guide the data selection process aligned to defined data quality thresholds. Based on our findings, practical recommendations are provided for data quality management in ERE. Scheme developers are encouraged to embed these in their methodologies to underpin transparent, robust labelling for product comparison.

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Uncovering the Calls of Data‐Deficient Masked Owls Using Morphology and Environmental Gradients - Nigel A. Jackett; Richard Schodde; Nicholas P. Leseberg; Stephen A. Murphy; Leo Joseph; Boyd J. Wykes; Michael K. Todd; Charley Gros; Rohan J. Bilney; Paul Barden; Peter Knock; Craig Dunne; et al. (Journal of Biogeography, 2025)
Aim To test whether vocal characteristics of little‐known and ‘lost’ owl species can be inferred from environmentally driven morphological and vocal correlations, using the Australian Masked Owl ( Tyto novaehollandiae ) as a model system. Location Australasia. Taxon Australian Masked Owl ( T. novaehollandiae superspecies, Tytonidae). Methods We fit linear models to examine the relationship between environmental variables (latitude, temperature, elevation) and wing length for 196 Australian Masked Owl specimens. We also examined the relationship between these environmental variables and acoustic characteristics (call duration and mean dominant frequency) from 700 calls recorded via passive acoustic monitoring. These datasets were then integrated to predict vocalisations for the Papuo‐Moluccan taxa Tyto aurantia , Tyto manusi , Tyto sororcula and Tyto novaehollandiae calabyi . Results Wing length of Australian Masked Owls was greater in females than in males ( R 2 = 0.480, p R 2 = 0.240, p R 2 = 0.211, p R 2 = 0.347, p = 0.013) and temperature ( R 2 = 0.347, p = 0.036). Mean dominant frequency increased at lower latitudes ( R 2 = 0.402, p R 2 = 0.391, p R 2 = 0.429, p = 0.032). Main Conclusions Environmental factors influencing morphology correlate with vocal traits, enabling predictions for species lacking reference calls. By correlating small datasets of data‐deficient species with larger datasets from better‐known relatives, our approach provides insights into the expected vocalisations of ‘lost’ Papuo‐Moluccan masked owls, challenges taxonomic boundaries, and offers a broadly applicable framework for biogeographic and taxonomic inference.

Recent Chemo-morphological coma evolution of comet 67P/Churyumov–Gerasimenko - Brian P. Murphy; Cyrielle Opitom; Colin Snodgrass; Sophie E. Deam; Léa Ferellec; Matthew Knight; Vincent Okoth; Bin Yang (Planetary and Space Science, 2025)

Correction to: Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Using low levels of antimicrobials and antiseptics as elicitors for environmental isolates to activate or re-activate antimicrobial producing biosynthetic gene clusters - Amy McLeman; Emma Murphy; Adam P. Roberts (Phytochemistry Letters, 2025)

Efficacy of Treating Nifedipine-Induced Shock with Hydroxocobalamin in a Swine Model - Christine Murphy; Michael Runyon; Michael Gellar; Nigel Rozario; Charity G. Patterson; William P. Kerns II (Journal of Medical Toxicology, 2025)

Limited responses of lizard assemblages to experimental fire regimes in an Australian tropical savanna - Angga Rachmansah; Keith Christian; Kimberley Day; Brett P. Murphy; Christine Schlesinger; Chava L. Weitzman; Alan N. Andersen (Ecology, 2025)
Disturbance is fundamental to ecosystem dynamics, and its management is foundational to effective ecosystem management for the conservation of biodiversity. Fire is a key agent of disturbance influencing faunal communities in many terrestrial ecosystems, and it underpins the conservation management of fire‐prone ecosystems. However, we have a limited understanding of how faunal communities in fire‐prone ecosystems respond to variation in fire frequency. Here, we use a long‐term fire experiment to investigate the effect of fire frequency on lizard assemblages in an Australian tropical savanna. We sampled lizards using pitfall traps, funnel traps, and direct searches in replicate ( n = 3) 1‐ha plots that had been burnt every 1, 3, or 5 years or left unburnt for 18 years. We found no significant variation in total lizard abundance or the collective abundances of mesic, semiarid, or widespread biogeographic groups. The abundance of only one of the five most common species was significantly related to fire frequency. Species richness decreased with increased fire frequency and showed a humped relationship with woody cover. Species composition was slightly better explained by variation in woody cover than by fire frequency, with both effects relatively weak. Although woody cover declined with increasing fire frequency, it varied markedly both within and among plots experiencing the same fire treatment, which explains why fire frequency was not as strong a predictor of variation in lizard assemblages as woody cover. Our findings show that the diverse lizard assemblage in our tropical savanna system exhibits a very limited response to variation in long‐term fire frequency and attribute this to the marked small‐scale variation in woody cover that was inherent under any fire treatment. We conclude that small‐scale patchiness in vegetation cover plays a critical role in the responses to fire of faunal species with relatively small foraging territories, reducing a need for larger scale fire mosaics under a “pyrodiversity begets biodiversity” paradigm.

Sediment dynamics in a dyke breach and across a tidally flooded land surface - Rachel A. Burns; Ryan P. Mulligan; Megan Elliott; Danika van Proosdij; Enda Murphy (Frontiers in Marine Science, 2025)
Nature-based solutions may be applied to restore or enhance coastal ecosystem function but should be considered carefully within the context of sediment transport that drives morphological change. This study, for the first time, assesses rates of sediment transport and deposition at a managed dyke realignment site in the critical time period immediately following the dyke breach and before the establishment of salt marsh vegetation. Field observations of water levels and current velocities, suspended sediment concentrations and deposition amounts were collected over 6 tidal cycles at spring tide in areas outside and in the flooded area. A numerical model with a flexible mesh (Delft3D-FM) is applied to simulate the sediment dynamics in a tidal channel, through a dyke breach and into an agricultural site in a macrotidal, mud-dominated estuary using a high-resolution grid to capture the complex topography and bathymetry. The model results enable the intricate spatio-temporal patterns of tidally-driven flows through the breach and over the intertidal flooded area to be revealed, and the important roles in controlling transport and sediment deposition patterns to be identified. The ditches and channels influence flow directions across the intertidal land surface, leading to high current velocities during flood tide, followed by periods of low velocity and particle settling that varies across the marsh surface. The sedimentation rates are estimated to be the same order of magnitude and slightly higher than the relative sea-level rise rate in this area, suggesting this type of marsh will be sustainable. Overall, the numerical results, combined with field observations, provide detailed quantification of the sediment-laden flow through a dyke breach and across the land surface, which is expected to be conducive to salt marsh plant development.

Bioaccumulations and biotransformations of azaspiracids from Amphidoma languida in the mussel Mytilus edulis - Elliot Murphy; Rafael Salas; Urban Tillmann; Jane Kilcoyne; Bernd Krock; Olivier P. Thomas (Chemosphere, 2025)

Museomics and Salvaged Feathers Piece Together the Evolutionary History and Conservation Genomics of the Elusive, Critically Endangered Night Parrot ( Pezoporus occidentalis ) - Heng Lin Yeap; Gunjan Pandey; Jeremy J. Austin; John G. Oakeshott; Christopher M. Hardy; Stephen A. Murphy; Nicholas P. Leseberg; Allan H. Burbidge; Kenny J. Travouillon; Leo Joseph; Anna M. Kearns (Molecular Ecology, 2025)
The Night Parrot is a critically endangered nocturnal bird of Australia's arid zone. The species was “lost” for most of the 20th century until its rediscovery in 1990. Extant populations are now known in eastern and western Australia, but the species has been extirpated from much of its historical range. Here we estimate critically needed Essential Biodiversity Variables (EBVs) for the Night Parrot from historical and opportunistically collected contemporary samples. We find little population structure across the species' range and evidence of recent connectivity between extant populations ~2000 km apart. Most eastern individuals show significant kinship with one another, as did two from an extinct population in southern Australia. Heterozygosity is similarly low in all extant populations but ten‐fold lower in the extinct population sampled. Coalescent modelling of effective population size ( Ne ) suggests that Night Parrot numbers were reasonably high until around 90 years ago when Ne crashed from ~10,000 to ~100. Current Ne is now at its lowest in the past several million years. Our findings will help guide the ongoing management of one of Australia's most threatened birds.

Expedited screening of methanotroph-microalgae cocultures for integrated biogas valorization and wastewater remediation - Loyal P. Murphy; Q. Peter He; Jin Wang (Journal of Environmental Management, 2025)

Responses of small mammals to prescribed low-intensity fire: Genetic insights from a northern Australian fire experiment - Alexander R. Carey; Georgina Neave; Teigan Cremona; Hugh F. Davies; Brett P. Murphy; Geoffrey J. Cary; Tiwi Rangers; Toby Barton; Sam C. Banks (Biological Conservation, 2025)

Environmental rating ecolabels: How does product categorization affect product ratings and potential interpretation? - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; David Sheffield; Richard Murphy (Journal of Industrial Ecology, 2025)
Environmental rating ecolabels (ERE) aim to present aggregated product environmental information to inform consumer choices. Performance ratings (e.g., A–E) are derived from life cycle assessment (LCA) results to enable comparison between products. The translation of LCA results to performance ratings requires definition of a common rating scale, either at a sector level or for subsets of products grouped by function (i.e., product categories). We investigate if and how assigning products to distinct categories influences final product ratings in ERE schemes. We consider if product categorization enables increased product differentiation and how the structure of categories affects the ratings awarded to products. Using a food sector case study, ratings were assigned to 2253 products based on aggregated environmental single scores derived from Agribalyse 3.1 and ratings obtained under three scenarios were compared: (1) no categorization—all products are placed on a single scale before rating; (2a) food group categorization—products are assigned to 11 food groups described in the Ciqual food composition database; and (2b) food subgroup categorization—products are assigned to 61 Ciqual food subgroups. We find that categorization has a significant influence on the final ratings, affecting at least 54% of products evaluated. Categorization restricts the range of products that can be compared but does not systematically improve differentiation within categories. For categorization to be used in ERE, categorization hierarchies need to be developed and harmonized at sector level reflecting consumer‐relevant substitution options. This study demonstrates that categorization is a key methodological consideration for ERE scheme developers.

Granulomatous enteritis due to Mycobacterium avium subsp avium in an alpaca - D. Murphy; C. Brady; P. Norton; A. Morgan; D. O’Brien; D. Bochynska; S. Alessandro Mignacca (Journal of Comparative Pathology, 2025)

Higher potential leaching of inorganic and organic additives from biodegradable compared to conventional agricultural plastic mulch film - Michaela K. Reay; Martine Graf; Madelyn Murphy; Gupeng Li; Changrong Yan; Mondira Bhattacharya; Henny Osbahr; Ji Ma; Wen Chengtao; Xiner Shi; Siyang Ren; Jixiao Cui; et al. (Journal of Hazardous Materials, 2025)

Influence of extended photoperiod using blue light masks on hypertrichosis, coat condition, and general health parameters in horses with pituitary pars intermedia dysfunction - S. Parmantier; P. Kyriazopoulou; M. McClendon; A. Adams; B.A. Murphy (Journal of Equine Veterinary Science, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Environmental rating ecolabels: Considerations for establishing a rating scale with categorical performance classes - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; Richard Murphy (Journal of Cleaner Production, 2025)

Stem Cell Markers LGR5, LGR4 and Their Immediate Signalling Partners are Dysregulated in Preeclampsia - Georgia P. Wong; Sunhild Hartmann; Olivia Nonn; Ping Cannon; Tuong-Vi Nguyen; Manju Kandel; Natasha de Alwis; Ciara N. Murphy; Natasha Pritchard; Ralf Dechend; Natalie J. Hannan; Stephen Tong; et al. (Stem Cell Reviews and Reports, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Large-scale pyrodiversity is not needed to beget ant diversity in an Australian tropical savanna - François Brassard; Brett P. Murphy; Simon Ferrier; Alan N. Andersen (Oecologia, 2025)
The hypothesis that pyrodiversity begets biodiversity is foundational to conservation management in fire-prone ecosystems and has received extensive research attention. However, empirical evidence for the hypothesis remains ambivalent. Moreover, few studies directly assess the key question of how much pyrodiversity is needed to conserve all species within a community. A novel way of addressing this is to use the biodiversity–maximisation approach developed for reserve selection as part of strategic conservation planning. We apply this approach to an ant dataset from a long-term fire experiment in northern Australia to establish how many of the six experimental fire treatments are required to represent all local ant diversity. We identified the treatment combinations required to maximise species richness and geometric mean abundance. We repeated this for six fire-activity classes based on cumulative fire intensity experienced by plots over the course of the experiment. We found that a very limited number of fire treatments or fire activity classes were needed to represent all of the highly diverse ant species and to maximise the geometric mean abundance of ants. We attribute this to the substantial small-scale heterogeneity of fire behaviour and vegetation structure within individual fire treatments. We conclude that high pyrodiversity at larger spatial scales is not required for sustaining ant biodiversity in our study system. We believe that a reserve selection approach is a powerful method for assessing how much pyrodiversity is needed to conserve biodiversity and recommend that it be applied to other taxa and other ecosystems.

A revised comprehensive inventory of landslides induced by the 2007 Aysén earthquake, Patagonia - Alejandra Serey; Sergio A. Sepúlveda; William Murphy; Gregory P. De Pascale; David N. Petley (Bulletin of Engineering Geology and the Environment, 2025)

Evaluation of foliar fungicides for Cercospora leaf spot management in table beet in New York - Pratibha Sharma; Sean P. Murphy; Julie R. Kikkert; Sarah J. Pethybridge (Crop Protection, 2025)

Rebuilding microbiomes: Facilitating animal-microbe interactions through ecological restoration and rewilding - P. Contos; H. Gibb; N.P. Murphy; S. Jellinek; J.L. Wood (Journal of Environmental Management, 2025)

The effect of bovine diets and stages of lactation on vitamin K content in butter and Cheddar cheese - Sitong Zhou; Jean-Christophe Jacquier; Raquel Cama-Moncunill; Hannah Furlong; Gabriela Gonzales Castillo; Peter Dunne; Mark Timlin; Deirdre Hennessy; Michael O’Donovan; Kieran McCarthy; Tom F. O’Callaghan; John P. Murphy; et al. (International Dairy Journal, 2025)

The influence of fire and termites on tree hollow development in an Australian tropical savanna - Ellen Rochelmeyer; Brett P. Murphy; Shaun R. Levick; Alyson M. Stobo-Wilson; Anna E. Richards (Forest Ecology and Management, 2025)

Declines in greater bilby (Macrotis lagotis) geographic range and realised niche are best explained by the invasive red fox (Vulpes vulpes) - Hayley M. Geyle; Alys R. Young; Brett P. Murphy; Chris R. Dickman; Christine Schlesinger; Kelly M. Dixon; Harry Moore; Sarah Legge; Jennifer Silcock; Naomi Indigo; Martin Dziminski; Bruce Greatwich; et al. (Biological Conservation, 2025)

Multimodal creativity assessments following acute and sustained microdosing of lysergic acid diethylamide - Robin J. Murphy; Rachael L. Sumner; Kate Godfrey; Acima Mabidikama; Reece P. Roberts; Frederick Sundram; Suresh Muthukumaraswamy (Psychopharmacology, 2025)
Introduction Enhanced creativity is often cited as an effect of microdosing (taking repeated low doses of a psychedelic drug). There have been recent efforts to validate the reported effects of microdosing, however creativity remains a difficult construct to quantify. Objectives The current study aimed to assess microdosing’s effects on creativity using a multimodal battery of tests as part of a randomised controlled trial of microdosing lysergic acid diethylamide (LSD). Methods Eighty healthy adult males were given 10 µg doses of LSD or placebo every third day for six weeks (14 total doses). Creativity tasks were administered at a drug-free baseline session, at a first dosing session during the acute phase of the drug’s effects, and in a drug-free final session following the six-week microdosing regimen. Creativity tasks were the Alternate Uses Test (AUT), Remote Associates Task (RAT), Consensual Assessment Technique (CAT), and an Everyday Problem-Solving Questionnaire (EPSQ). Results No effect of drug by time was found on the AUT, RAT, CAT, or EPSQ. Baseline vocabulary skill had a significant effect on AUT and RAT scores. Conclusions Despite participants reporting feeling more creative on dose days, objective measurement found no acute or durable effects of the microdosing protocol on creativity. Possible explanations of these null findings are that laboratory testing conditions may negatively affect ability to detect naturalistic differences in creative performance, the tests available do not capture the facets of creativity that are anecdotally affected by microdosing, or that reported enhancements of creativity are placebo effects.

Curcumin Improves Hippocampal Cell Bioenergetics, Redox and Inflammatory Markers, and Synaptic Proteins, Regulating Mitochondrial Calcium Homeostasis - Claudia Jara; Angie K. Torres; Han S. Park-Kang; Lisette Sandoval; Claudio Retamal; Alfonso Gonzalez; Micaela Ricca; Sebastián Valenzuela; Michael P. Murphy; Nibaldo C. Inestrosa; Cheril Tapia-Rojas (Neurotoxicity Research, 2025)

Antimicrobial resistant Enterobacterales of clinical importance in mute swans - Aneta Kovarova; Graham Prole; Maeve Louise Farrell; Mark Maguire; Louise Catherine Murphy; Alexandra Chueiri; Louise O'Connor; Georgios Miliotis; Dearbháile Morris; Liam P. Burke (Science of The Total Environment, 2025)

Bioactivity of Amphidinol-Containing Extracts of Amphidinium carterae Grown Under Varying Cultivation Conditions - Maria Elena Barone; Elliot Murphy; David Fierli; Floriana Campanile; Gerard T. A. Fleming; Olivier P. Thomas; Nicolas Touzet (Current Microbiology, 2024)

Genotypic and phenotypic characterisation of asymptomatic bacteriuria (ABU) isolates displaying bacterial interference against multi-drug resistant uropathogenic E. Coli - Ciara Kenneally; Craig P. Murphy; Roy D. Sleator; Eamonn P. Culligan (Archives of Microbiology, 2024)
Escherichia coli can colonise the urogenital tract of individuals without causing symptoms of infection, in a condition referred to as asymptomatic bacteriuria (ABU). ABU isolates can protect the host against symptomatic urinary tract infections (UTIs) by bacterial interference against uropathogenic E. coli (UPEC). The aim of this study was to investigate the genotypic and phenotypic characteristics of five ABU isolates from midstream urine samples of adults. Comparative genomic and phenotypic analysis was conducted including an antibiotic resistance profile, pangenome analysis, and a putative virulence profile. Based on the genome analysis, the isolates consisted of one from phylogroup A, three from phylogroup B2, and one from phylogroup D. Two of the isolates, PUTS 58 and SK-106-1, were noted for their lack of antibiotic resistance and virulence genes compared to the prototypic ABU strain E. coli 83,972. This study provides insights into the genotypic and phenotypic profiles of uncharacterised ABU isolates, and how relevant fitness and virulence traits can impact their potential suitability for therapeutic bacterial interference.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

P19-89 Toxicokinetic and alternative methods to support dog study waiver decision making in pesticide risk assessment: triclopyr as a case study - N. Printemps; P. Deford; J. Domoradzki; M. Himmelstein; R. Mingoia; L. Murphy; M. Corvaro (Toxicology Letters, 2024)

Corticospinal and spinal responses following a single session of lower limb motor skill and resistance training - Alex Woodhead; Christopher Rainer; Jessica Hill; Colm P. Murphy; Jamie S. North; Dawson Kidgell; Jamie Tallent (European Journal of Applied Physiology, 2024)

A clear case for dust obscuration of the lunar retroreflectors - Sanchit Sabhlok; James B.R. Battat; Nicholas R. Colmenares; Daniel P. Gonzales; Thomas W. Murphy (Icarus, 2024)

Nestbox use indicates declining arboreal mammals in an Australian savanna may be limited by tree hollow availability - Leigh-Ann Woolley; Ian J. Radford; Teigan Cremona; John C.Z. Woinarski; Brydie M. Hill; Michael J. Lawes; Brett P. Murphy (Forest Ecology and Management, 2024)

Everolimus alleviates CD4+ T cell inflammation by regulating autophagy and cellular redox homeostasis - Jack Donato Rockhold; Heather Marszalkowski; Marco Sannella; Kaleigh Gibney; Lyanne Murphy; Emelia Zukowski; Gabriella H. Kalantar; Sara SantaCruz-Calvo; Samantha N. Hart; Madison K. Kuhn; Jingting Yu; Olivia Stefanik; et al. (GeroScience, 2024)

Parsing the toxicity paradox: Composition and duration of exposure alter predicted oil spill effects by orders of magnitude - Deborah P. French-McCay; Hilary J. Robinson; Julie E. Adams; Matthew A. Frediani; Matthew J. Murphy; Cheryl Morse; Melissa Gloekler; Thomas F. Parkerton (Marine Pollution Bulletin, 2024)

Temperature-controlled 3D printing of dairy structures using cold-renneted protein-fortified milk - Ricardo Uribe-Alvarez; Craig P. Murphy; Caroline Coleman-Vaughan; Norah O'Shea (Journal of Food Engineering, 2024)

Functional reorganization of North American wintering avifauna - Juan P. Quimbayo; Stephen J. Murphy; Marta A. Jarzyna (Ecology Letters, 2024)
Wintering birds serve as vital climate sentinels, yet they are often overlooked in studies of avian diversity change. Here, we provide a continental‐scale characterization of change in multifaceted wintering avifauna and examine the effects of climate change on these dynamics. We reveal a strong functional reorganization of wintering bird communities marked by a north–south gradient in functional diversity change, along with a superimposed mild east–west gradient in trait composition change. Assemblages in the northern United States saw contractions of the functional space and increases in functional evenness and originality, while the southern United States saw smaller contractions of the functional space and stasis in evenness and originality. Shifts in functional diversity were underlined by significant reshuffling in trait composition, particularly pronounced in the western and northern United States. Finally, we find strong contributions of climate change to this functional reorganization, underscoring the importance of wintering birds in tracking climate change impacts on biodiversity.

Impact of feeding regimes and lactation stage on sensory attributes of Cheddar cheese - Lauren McGuinness; Mark Timlin; John P. Murphy; Deirdre Hennessy; Ellen Fitzpatrick; Kieran McCarthy; Michael O'Donovan; Tom F. O'Callaghan; Kieran N. Kilcawley; E. Dolores O'Riordan; Andre Brodkorb; Jeremiah J. Sheehan; et al. (Food Research International, 2024)

ELSSIE: A compact stereo spectral imager for planetary surface morphology and composition - Scott L. Murchie; Frank P. Seelos; Bethany L. Ehlmann; John D. Boldt; Lawrence E. Brown; Jacob M. Greenberg; Karl A. Hibbitts; W. Jeffrey Lees; David M. Linko; Joseph J. Linden; Graham P. Murphy; Jorge I. Núñez; et al. (Planetary and Space Science, 2024)

A toxicological assessment of spermidine trihydrochloride produced using an engineered strain of Saccharomyces cerevisiae - Paola P. Chrysostomou; Elaine L. Freeman; Mary M. Murphy; Rui Pereira; David J. Esdaile; Patrick Keohane (Food and Chemical Toxicology, 2024)

Nitrate leaching on Irish grassland dairy farms: A review - D.J. Murphy; P. Dillon; M. O’ Donovan; L. Shalloo; E. Ruelle (European Journal of Agronomy, 2024)

Comparison of reactive transport and non-equilibrium modeling approaches for the estimation of nitrate leaching under large water application events - Nicholas P. Murphy; Alex Furman; Shany-Ben Moshe; Helen E. Dahlke (Journal of Hydrology, 2024)

An epigenome-wide association study of child appetitive traits and DNA methylation - Holly A. Harris; Chloe Friedman; Anne P. Starling; Dana Dabelea; Susan L. Johnson; Bernard F. Fuemmeler; Dereje Jima; Susan K. Murphy; Cathrine Hoyo; Pauline W. Jansen; Janine F. Felix; Rosa H. Mulder (Appetite, 2023)

An extreme model of fertility in sheep demonstrates the basis of controversies surrounding antral follicle count and circulating concentrations of anti-Müllerian hormone as predictors of fertility in ruminants - Robert A. Cushman; Hannah K. Yake; Alexandria P. Snider; Clay A. Lents; Thomas W. Murphy; Bradley A. Freking (Animal Reproduction Science, 2023)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Stabilisation of evaporation and spray drying processes with municipal or reverse osmosis water as an entry point for chlorate during manufacture of skim milk powder - William P. McCarthy; Eoin Murphy; Martin Danaher; Christine O'Connor; John T. Tobin (International Dairy Journal, 2023)

Identification and characterization of Phaseolus vulgaris endornavirus 1, 2 and 3 in common bean cultivars of East Africa - Thomas J. Brine; Sam Crawshaw; Alex M. Murphy; Adrienne E. Pate; John P. Carr; Francis O. Wamonje (Virus Genes, 2023)
Persistent viruses include members of the family Endornavirus that cause no apparent disease and are transmitted exclusively via seed or pollen. It is speculated that these RNA viruses may be mutualists that enhance plant resilience to biotic and abiotic stresses. Using reverse transcription coupled polymerase chain reactions, we investigated if common bean ( Phaseolus vulgaris L.) varieties popular in east Africa were hosts for Phaseolus vulgaris endornavirus (PvEV) 1, 2 or 3. Out of 26 bean varieties examined, four were infected with PvEV1, three were infected with both PvEV1 and PvEV2 and three had infections of all three (PvEV) 1, 2 and 3. Notably, this was the first identification of PvEV3 in common bean from Africa. Using high-throughput sequencing of two east African bean varieties (KK022 and KK072), we confirmed the presence of these viruses and generated their genomes. Intra- and inter-species sequence comparisons of these genomes with comparator sequences from GenBank revealed clear species demarcation. In addition, phylogenetic analyses based on sequences generated from the helicase domains showed that geographical distribution does not correlate to genetic relatedness or the occurrence of endornaviruses. These findings are an important first step towards future investigations to determine if these viruses engender positive effects in common bean, a vital crop in east Africa.

Evaluation of ionic calcium and protein concentration on heat- and cold-induced gelation of whey protein isolate gels as a potential food formulation for 3D food printing - Ricardo Uribe-Alvarez; Craig P. Murphy; Caroline Coleman-Vaughan; Norah O'Shea (Food Hydrocolloids, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Fire influences ant diversity by modifying vegetation structure in an A ustralian tropical savanna - François Brassard; Magen J. Pettit; Brett P. Murphy; Alan N. Andersen (Ecology, 2023)
Fire is a dominant ecological force shaping many faunal communities globally. Fire affects fauna either directly, such as by killing individuals, or indirectly, such as by modifying vegetation structure. Vegetation structure itself also modulates fire frequency and intensity. As such, faunal responses to fire need to be seen through the lens of variable fire activity and vegetation structure. Here, we incorporate information on fire activity and vegetation structure to enhance an understanding of the response of ants to long‐term (17‐year) experimental fire treatments in an extremely fire‐prone tropical savanna in northern Australia. Previous analysis revealed limited divergence in ant communities after 5 years of experimental fire treatment. Hence, we first investigated the extent to which ant communities diverged over a subsequent 12 years of treatment. We then assessed the relative contribution of fire treatment, cumulative fire intensity (fire activity), and woody cover to responses of ant species frequency of occurrence, richness, and composition. We found that, even after 17 years, fire treatments explained little variation in any ant response variable. In contrast, woody cover was a strong predictor for all of them, while fire activity was a moderate predictor for abundance and richness. Ant species occurrence and richness increased in open habitats receiving higher levels of fire activity, compared with plots with higher vegetation cover experiencing low (or no) fire activity. Moreover, species composition differed between plots with high and low vegetation cover. Our findings provide experimental support to the principle that the effects of fire on fauna are primarily indirect, via its effect on vegetation structure. Furthermore, our results show that a “uniform” fire regime does not have uniform impacts on the ant fauna, because of variability imposed by interactions between vegetation structure and fire activity. This helps to explain why there is often a weak relationship between pyrodiversity and biodiversity, and it lessens the need for active management of pyrodiversity to maintain biodiversity.

Production of the dinoflagellate Amphidoma languida in a large scale photobioreactor and structure elucidation of its main metabolite AZA-39 - Rafael Salas; Elliot Murphy; Roisin Doohan; Urban Tillmann; Olivier P. Thomas (Harmful Algae, 2023)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

Reconstructing mechanisms of extinctions to guide mammal conservation biogeography - Sean Tomlinson; Mark V. Lomolino; John C. Z. Woinarski; Brett P. Murphy; Elizabeth Reed; Chris N. Johnson; Sarah Legge; Kristofer M. Helgen; Stuart C. Brown; Damien A. Fordham (Journal of Biogeography, 2023)
An emerging research program on population and geographic range dynamics of Australia's mammals illustrates an approach to better understand and respond to geographic range collapses of threatened wildlife in general. In 1788, Europeans colonized an Australia with a diverse and largely endemic mammal fauna, where many species that are now extinct or threatened were common and widespread. Subsequent population declines, range collapses and extinctions were caused by introduced predators and herbivores, altered land use, modified fire regimes and the synergies between these threats. Declines in population and range size continue for many Australian mammals despite legislative protection and conservation interventions. Here, we propose an approach that integrates museum data and other historical records into process‐explicit macroecological models to better resolve mammal distributions and abundances as they were at European arrival. We then illustrate how this integrative approach can identify the likely synergistic mechanisms causing mammal population declines across these and other landscapes. This emerging research approach, undertaken with fine temporal and spatial resolution, but at large geographic scales, will provide valuable insights into the different pathways to, and drivers of, extinction. Such insights may, in turn, underpin conservation strategies based on a process‐explicit understanding of population decline and range collapse under alternative scenarios of impending climate and environmental change. Given that similar information is available for other regional biotas, the approach we describe here can be adapted to conserve threatened wildlife in other regions across the globe.

Physical and geochemical reconstruction of a 2.35–2.1 Ga volcanic arc (Toumodi Greenstone Belt, Ivory Coast, West Africa) - P.C. Hayman; P. Bolz; G. Senyah; E. Tegan; S. Denyszyn; D.T. Murphy; M.W. Jessell (Precambrian Research, 2023)

Towards credible, evidence-based environmental rating ecolabels for consumer products: A proposed framework - Maëlys Courtat; P. James Joyce; Sarah Sim; Jhuma Sadhukhan; Richard Murphy (Journal of Environmental Management, 2023)

Multimethod provenance analysis using detrital zircon and rutile U-Pb geochronology across Devonian basin systems in the Tasmanides of eastern Australia - P. Asmussen; D.A. Gust; S.E. Bryan; D. Purdy; D. Murphy; C.M. Allen (Gondwana Research, 2023)

Pyrodiversity trade-offs: A simulation study of the effects of fire size and dispersal ability on native mammal populations in northern Australian savannas - Hugh F. Davies; Casey Visintin; Brett P. Murphy; Euan G. Ritchie; Sam C. Banks; Ian D. Davies; David M.J.S. Bowman (Biological Conservation, 2023)

Validation and Comparison of Nutrient Intakes from Two Dietary Questionnaires Developed for the Multiethnic Cohort Study - Lynne R. Wilkens; Minji Kang; Song-Yi Park; Adam Sawyer; Carol J. Boushey; Donna Lyn M. Au; Hee-Young Paik; Loïc Le Marchand; Christopher A. Haiman; Laurence N. Kolonel; Suzanne P. Murphy (Journal of the Academy of Nutrition and Dietetics, 2023)

Correction to: Mapping of a novel major effect Hessian fly field partial-resistance locus in southern soft red winter wheat line LA03136E71 - Z. J. Winn; R. Acharya; K. Merrill; J. Lyerly; G. Brown‑Guedira; S. Cambron; S. H. Harrison; D. Reisig; J. P. Murphy (Theoretical and Applied Genetics, 2023)

Pyric Herbivory and the Nexus Between Forage, Fire and Native and Introduced Large Grazing Herbivores in Australian Tropical Savannas - Angela M. Reid; Brett P. Murphy; Tom Vigilante; David M. J. S. Bowman (Ecosystems, 2023)
Earth’s tropical savannas typically support high biomass of diverse grazing herbivores that depend on a highly fluctuating resource: high-quality forage. An annual wet–dry cycle, fire and herbivory combine to influence forage quality and availability throughout the year. In the savannas of northern Australia, a depauperate suite of large native (marsupial) herbivores (wallaroos [ Osphranter spp.] and the agile wallaby [ Notamacropus agilis ]) compete for resources with non-native large herbivores introduced in the late nineteenth century, particularly bovines (feral and managed cattle [ Bos spp.] and feral water buffalo [ Bubalus bubalis ]) that now dominate the landscape. Anecdotal reports of recent population declines of large macropods and negative impacts of bovines highlight the need to better understand the complex relationship between forage, fire and abundance of native and introduced large herbivores. The pyric herbivory conceptual model, which posits complex feedbacks between fire and herbivory and was developed outside Australia, predicts that native and introduced large herbivores will both respond positively to post-fire forage production in Australian savannas where they co-occur. We used grazing exclosures, forage biomass and nutrient analyses and motion-sensor camera-trapping to evaluate the overall robustness of the pyric herbivory model in the Australian context, specifically whether forage quantity and quality are impacted by herbivory, season and fire activity, and which forage attributes most influence large grazing herbivore abundance. Forage quantity, as measured by live, dead and total herbaceous biomass and proportion of biomass alive, was higher inside herbivore exclosures, even at relatively low densities of herbivores. Forage quality, as measured by fibre content, was not affected by herbivory, however, crude protein content of live herbaceous biomass was greater outside herbivore exclosures. Recent fire was an important predictor of all measures of forage quantity and quality. Recent fire occurrence decreased overall quantity (biomass) but increased quality (decreased fibre content and increased crude protein content); late dry season fires resulted in forage with the highest crude protein content. The predictions of the pyric herbivory conceptual model are consistent with observations of the feeding behaviour of introduced bovines and some large macropods in northern Australian savannas, lending support to the global generality of pyric herbivory in fire-prone grassy biomes.

Fire severity is an important driver of land snail declines after the black summer bushfires in Australia - Orsi Decker; Junn Kitt Foon; Frank Köhler; Adnan Moussalli; Nicholas P. Murphy; Peter T. Green (Biological Conservation, 2023)

Corticospinal and spinal adaptations following lower limb motor skill training: a meta-analysis with best evidence synthesis - Alex Woodhead; Jamie S. North; Jessica Hill; Colm P. Murphy; Dawson J. Kidgell; Jamie Tallent (Experimental Brain Research, 2023)

Agricultural managed aquifer recharge (Ag-MAR)—a method for sustainable groundwater management: A review - Elad Levintal; Maribeth L. Kniffin; Yonatan Ganot; Nisha Marwaha; Nicholas P. Murphy; Helen E. Dahlke (Critical Reviews in Environmental Science and Technology, 2023)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Exploring metapopulation‐scale suppression alternatives for a global invader in a river network experiencing climate change - Brian D. Healy; Phaedra Budy; Charles. B. Yackulic; Brendan P. Murphy; Robert C. Schelly; Mark C. McKinstry (Conservation Biology, 2023)
Invasive species can dramatically alter ecosystems, but eradication is difficult, and suppression is expensive once they are established. Uncertainties in the potential for expansion and impacts by an invader can lead to delayed and inadequate suppression, allowing for establishment. Metapopulation viability models can aid in planning strategies to improve responses to invaders and lessen invasive species’ impacts, which may be particularly important under climate change. We used a spatially explicit metapopulation viability model to explore suppression strategies for ecologically damaging invasive brown trout ( Salmo trutta ), established in the Colorado River and a tributary in Grand Canyon National Park. Our goals were to estimate the effectiveness of strategies targeting different life stages and subpopulations within a metapopulation; quantify the effectiveness of a rapid response to a new invasion relative to delaying action until establishment; and estimate whether future hydrology and temperature regimes related to climate change and reservoir management affect metapopulation viability and alter the optimal management response. Our models included scenarios targeting different life stages with spatially varying intensities of electrofishing, redd destruction, incentivized angler harvest, piscicides, and a weir. Quasi‐extinction (QE) was obtainable only with metapopulation‐wide suppression targeting multiple life stages. Brown trout population growth rates were most sensitive to changes in age 0 and large adult mortality. The duration of suppression needed to reach QE for a large established subpopulation was 12 years compared with 4 with a rapid response to a new invasion. Isolated subpopulations were vulnerable to suppression; however, connected tributary subpopulations enhanced metapopulation persistence by serving as climate refuges. Water shortages driving changes in reservoir storage and subsequent warming would cause brown trout declines, but metapopulation QE was achieved only through refocusing and increasing suppression. Our modeling approach improves understanding of invasive brown trout metapopulation dynamics, which could lead to more focused and effective invasive species suppression strategies and, ultimately, maintenance of populations of endemic fishes.

Use of Enrofloxacin and Hydrotherapy in the Management of Fibrodysplasia Ossificans Progressiva (FOP) in a Savannah Cat - Kim L. Jacobsen; Valerie Wiebe; Autumn P. Davidson; Brian G. Murphy; Jr. Roy R. Pool (Topics in Companion Animal Medicine, 2023)

USUAL Watershed Tools: A new geospatial toolkit for hydro-geomorphic delineation - Scott R. David; Brendan P. Murphy; Jonathan A. Czuba; Muneer Ahammad; Patrick Belmont (Environmental Modelling & Software, 2023)

Unified understanding of intrinsic and extrinsic controls of dissolved organic carbon reactivity in aquatic ecosystems - Martin Berggren; François Guillemette; Magdalena Bieroza; Ishi Buffam; Anne Deininger; Jeffrey A. Hawkes; Dolly N. Kothawala; Richard LaBrie; Jean‐François Lapierre; Kathleen R. Murphy; Enass S. Al‐Kharusi; Mayra P. D. Rulli; et al. (Ecology, 2022)
Despite our growing understanding of the global carbon cycle, scientific consensus on the drivers and mechanisms that control dissolved organic carbon (DOC) turnover in aquatic systems is lacking, hampered by the mismatch between research that approaches DOC reactivity from either intrinsic (inherent chemical properties) or extrinsic (environmental context) perspectives. Here we propose a conceptual view of DOC reactivity in which the combination of intrinsic and extrinsic factors controls turnover rates and determines which reactions will occur. We review three major types of reactions (biological, photochemical, and flocculation) from an intrinsic chemical perspective and further define the environmental features that modulate the expression of chemically inherent reactivity potential. Finally, we propose hypotheses of how extrinsic and intrinsic factors together shape patterns in DOC turnover across the land‐to‐ocean continuum, underscoring that there is no intrinsic DOC reactivity without environmental context. By acknowledging the intrinsic–extrinsic control duality, our framework intends to foster improved modeling of DOC reactivity and its impact on ecosystem services.

Boundary layer hydrodynamics of patchy biofilms - Elizabeth A. K. Murphy; Julio M. Barros; Michael P. Schultz; Karen A. Flack; Cecily N. Steppe; Matthew A. Reidenbach (Biofouling, 2022)

Guiding principles for integrating stakeholder‐based data into marine fisheries decision‐making with a focus on USA fisheries management - Robert Murphy; Michael Downs; Nathan Wolf; Bradley P. Harris (Fish and Fisheries, 2022)
The propensity for fisheries management agencies in the United States to collect or request stakeholder‐based data has grown considerably in the last decade. While systems are in place for the review and use of biological data in management, there is far less structure to the integration of non‐economic social data. Here, we present a framework for characterizing the applicability of various forms of social data in regulatory processes, documents, and decisions. The social data landscape is presented as a simple framework for understanding the temporal, spatial, and impact scope of policy actions and how different kinds of social data can inform an array of action types and play important roles in management. We conclude with recommendations for practitioners and managers who seek to incorporate different types of stakeholder input into their processes and provide researchers with guidelines when weighing the trade‐offs of unique methodologies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

2‐Aminoethylphosphonate utilization in Pseudomonas putida BIRD ‐1 is controlled by multiple master regulators - Andrew R. J. Murphy; David J. Scanlan; Yin Chen; Gary D. Bending; John P. Hammond; Elizabeth M. H. Wellington; Ian D. E. A. Lidbury (Environmental Microbiology, 2022)
Summary Bacteria possess various regulatory mechanisms to detect and coordinate a response to elemental nutrient limitation. In pseudomonads, the two‐component system regulators CbrAB, NtrBC and PhoBR, are responsible for regulating cellular response to carbon (C), nitrogen (N) and phosphorus (P) respectively. Phosphonates are reduced organophosphorus compounds produced by a broad range of biota and typified by a direct C‐P bond. Numerous pseudomonads can use the environmentally abundant phosphonate species 2‐aminoethylphosphonate (2AEP) as a source of C, N, or P, but only PhoBR has been shown to play a role in 2AEP utilization. On the other hand, utilization of 2AEP as a C and N source is considered substrate inducible. Here, using the plant‐growth‐promoting rhizobacterium Pseudomonas putida BIRD‐1 we present evidence that 2AEP utilization is under dual regulation and only occurs upon depletion of C, N, or P, controlled by CbrAB, NtrBC, or PhoBR respectively. However, the presence of 2AEP was necessary for full gene expression, i.e. expression was substrate inducible. Mutation of a LysR‐type regulator, termed AepR, upstream of the 2AEP transaminase‐phosphonatase system (PhnWX), confirmed this dual regulatory mechanism. To our knowledge, this is the first study identifying coordination between global stress response and substrate‐specific regulators in phosphonate metabolism.

Barriers to Achieving Conservation Engineering Goals in Commercial Trawl Fisheries - Robert Murphy; Noëlle Yochum; Nathan Wolf; Anita C. Kroska; Bradley P. Harris (Frontiers in Marine Science, 2022)
The advancement of conservation practices in global trawl fisheries has been impeded in part by a lack of a collective understanding of the most relevant and broad-scale knowledge-needs, along with the identification of potential barriers to addressing these knowledge-needs. Using both an online survey and an in-person workshop, we engaged a diversity of fishing industry stakeholders including scientists, technology companies, trawl net makers, and fishermen working with North Pacific, United States, trawl fisheries to identify and prioritize areas in which further knowledge is required for successful implementation of conservation engineering practices. In addition, we identified barriers to addressing these knowledge-needs. Knowledge-needs related to fishing gear performance were identified among the top priorities, including several areas targeted at improving fishing efficiency that could further advance the sustainability of well-managed trawl fisheries. To better understand the composition and behavior of target versus non-target catch, workshop participants identified the importance of closing data and technology gaps. This highlights areas for potential collaboration between fishermen, researchers, and technology companies to address research prioritized by the end-user. Further, results from the workshop emphasized a need for industry-driven training and workshops focused on elevating fishermen skill for newer entrants through peer-learning and knowledge-sharing to achieve objectives like better non-target avoidance and increased fishing efficiency of the target species. Addressing these prioritized knowledge-needs, by first working toward overcoming the industry-identified barriers, may aid in increasing uptake of conservation practices, thereby contributing to the long-term sustainability of these fisheries and associated social-ecological systems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Mapping of a novel major effect Hessian fly field partial-resistance locus in southern soft red winter wheat line LA03136E71 - Z. J. Winn; R. Acharya; K. Merrill; J. Lyerly; G. Brown-Guedira; S. Cambron; S. H. Harrison; D. Reisig; J. P. Murphy (Theoretical and Applied Genetics, 2021)

Unexpected overlapping use of tree hollows by birds, reptiles and declining mammals in an Australian tropical savanna - Cara E. Penton; Ian J. Radford; Leigh-Ann Woolley; Brenton von Takach; Brett P. Murphy (Biodiversity and Conservation, 2021)

Utilising grassland management and climate data for more accurate prediction of herbage mass using the rising plate meter - D. J. Murphy; P. Shine; B. O’. Brien; M. O’. Donovan; M. D. Murphy (Precision Agriculture, 2021)

Immunomodulatory properties of characellide A on human peripheral blood mononuclear cells - Simone Marcella; Sam Afoullouss; Olivier P. Thomas; A. Louise Allcock; Paul V. Murphy; Stefania Loffredo (Inflammopharmacology, 2021)
Marine sponges and their associated microbiota are multicellular animals known to produce metabolites with interesting pharmacological properties playing a pivotal role against a plethora of pathologic disorders such as inflammation, cancer and infections. Characellide A and B belong to a novel class of glycolipopeptides isolated from the deep sea marine sponge Characella pachastrelloides . In this study, we have evaluated the effects of characellide A and B on cytokine and chemokine release from human peripheral blood mononuclear cells (PBMC). Characellide A induces a concentration- and time-dependent CXCL8, IL-6 and TNF-α release from PBMC. This production is mediated by the induction of gene transcription. Moreover, cytokine/chemokine release induced by characellide A from PBMC is CD1d-dependent because a CD1d antagonist, 1,2-bis(diphenylphosphino)ethane [DPPE]-polyethylene glycolmonomethylether [PEG], specifically inhibits characellide A-induced activation of PBMC. In conclusion, characellide A is a novel modulator of adaptative/innate immune responses. Further studies are needed to understand its potential pharmacological application.

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Liver injury during rivaroxaban treatment in a patient with AL amyloidosis - Alan Marrinan; L. Shackleton; C. Kelly; M. Lavin; S. Glavey; P. Murphy; J. Quinn (European Journal of Clinical Pharmacology, 2021)

Corrigendum: Future Risk for Southern Ocean Ecosystem Services Under Climate Change - Rachel D. Cavanagh; Jess Melbourne-Thomas; Susie M. Grant; David K. A. Barnes; Kevin A. Hughes; Svenja Halfter; Michael P. Meredith; Eugene J. Murphy; Rowan Trebilco; Simeon L. Hill (Frontiers in Marine Science, 2021)

Effects of voluntary wheel running on mitochondrial content and dynamics in rat skeletal muscle - Barnaby P. Frankish; Petra Najdovska; Hongyang Xu; Stefan G. Wette; Robyn M. Murphy (Journal of Muscle Research and Cell Motility, 2021)

Global drivers of recent diversification in a marine species complex - Catarina N.S. Silva; Nicholas P. Murphy; James J. Bell; Bridget S. Green; Guy Duhamel; Andrew C. Cockcroft; Cristián E. Hernández; Jan M. Strugnell (Molecular Ecology, 2021)
Investigating historical gene flow in species complexes can indicate how environmental and reproductive barriers shape genome divergence during speciation. The processes influencing species diversification under environmental change remain one of the central focal points of evolutionary biology, particularly for marine organisms with high dispersal potential. We investigated genome‐wide divergence, introgression patterns and inferred demographic history between species pairs of all six extant rock lobster species ( Jasus spp.), which have a long larval duration of up to two years and have populated continental shelf and seamount habitats around the globe at approximately 40 o S. Genetic differentiation patterns reflected geographic isolation and the environment (i.e. habitat structure). Eastern Pacific species ( J. caveorum and J. frontalis ) were geographically more distant and genetically more differentiated from the remaining four species. Species associated with continental shelf habitats shared a common ancestry, but are geographically distant from one another. Similarly, species associated with island/seamount habitats in the Atlantic and Indian Oceans shared a common ancestry, but are also geographically distant. Benthic temperature was the environmental variable that explained most of the genetic differentiation (F ST ), while controlling for the effects of geographic distance. Eastern Pacific species retained a signal of strict isolation following ancient migration, whereas species pairs from Australia and Africa, and seamounts in the Indian and Atlantic oceans, included events of introgression after secondary contact. Our results reveal important effects of habitat and demographic processes on the recent divergence of species within the genus Jasus , providing one of the first empirical studies of genome‐wide drivers of diversification that incorporates all extant species in a marine genus with long pelagic larval duration.

Microsatellite Markers Reveal Unprecedented High Frequencies of Hybridization among Typha Species in the Midwestern US - Pamela Geddes; Lynnette Murphy; Yaiyr Astudillo-Scalia; Davis Blasini; Sarah Nugent; María Jazmín Ríos; Aaron E. Schirmer; Joel P. Olfelt (Wetlands, 2021)

Future Risk for Southern Ocean Ecosystem Services Under Climate Change - Rachel D. Cavanagh; Jess Melbourne-Thomas; Susie M. Grant; David K. A. Barnes; Kevin A. Hughes; Svenja Halfter; Michael P. Meredith; Eugene J. Murphy; Rowan Trebilco; Simeon L. Hill (Frontiers in Marine Science, 2021)
The Southern Ocean supports ecosystem services that are important on a global scale. Climate change and human activities (tourism, fishing, and research) will affect both the demand for, and the provision of, these services into the future. Here we synthesize recent assessments of the current status and expected future climate-driven changes in Southern Ocean ecosystems and evaluate the potential consequences of these changes for the provision of ecosystem services. We explore in detail three key services (the ‘blue carbon’ pathway, the Antarctic krill fishery, and Antarctic tourism), tracing the consequences of climate change from physical drivers through biological impacts to the benefits to humans. We consider potential non-climatic drivers of change, current and future demands for the services, and the main global and regional policy frameworks that could be used to manage risks to the provision of these services in a changing climate. We also develop a formal representation of the network of interactions between the suite of potential drivers and the suite of services, providing a framework to capture the complexity of this network and its embedded feedback loops. Increased consideration of the linkages and feedbacks between drivers and ecosystem services will be required to underpin robust management responses into the future.

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

Impacts on freshwater macrophytes produced by small invertebrate herbivores: Afrotropical and Neotropical wetlands compared - M. Celeste Franceschini; Kevin J. Murphy; Isabel Moore; Michael P. Kennedy; Fedra S. Martínez; Frank Willems; M. Laura De Wysiecki; Henry Sichingabula (Hydrobiologia, 2020)

Environmental DNA metabarcoding provides enhanced detection of the European eel Anguilla anguilla and fish community structure in pumped river catchments - Nathan P. Griffiths; Jonathan D. Bolland; Rosalind M. Wright; Leona A. Murphy; Robert K. Donnelly; Hayley V. Watson; Bernd Hänfling (Journal of Fish Biology, 2020)
The European eel Anguilla anguilla (eel hereafter) is critically endangered and has a catadromous life cycle, which means adult eels that live in pumped catchments must pass through pumps during their downstream spawning migration. Policy makers are currently lacking detailed site‐by‐site eel distribution information to estimate the overall impact of individual pumping stations on eel escapement, and as such lack the data to enable informed prioritisation of pumping station management and targeted mitigation. This study investigated whether environmental DNA (eDNA) metabarcoding can provide increased detection sensitivity for eel and fish community structure in highly regulated pumped catchments, when compared directly to current standard practice fish survey protocols (seine netting/electric fishing). Eels were detected in 14 of 17 sites (82.4%) using eDNA metabarcoding in contrast to 3 of 17 sites (17.6%) using traditional catch methods. In addition, when using eDNA monitoring, species richness was higher in 16 of 17 sites (94.1%), and site occupancy was greater than or equal to traditional methods for 23 of 26 of the fish species detected (88.5%). Although eDNA methods presented significantly higher average species richness and species site occupancy overall, eDNA and catch methods were positively correlated in terms of species richness and site occupancy. It was therefore found that eDNA metabarcoding was a high‐sensitivity method for detecting eels in pumped catchments while also increasing the detection of overall fish community structure compared to traditional catch methods. In addition, this study highlights how eDNA monitoring is especially suited to increase the detection of particular species, with traditional methods sufficient for others. This high sensitivity, coupled with the ability to sample multiple sites in a short time frame, suggests that eDNA metabarcoding workflows could be invaluable tools when prioritising pumping station management.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Potential of tropical macroalgae from French Polynesia for biotechnological applications - Mayalen Zubia; Olivier P. Thomas; Stéphanie Soulet; Marina Demoy-Schneider; Denis Saulnier; Solène Connan; Elliot C. Murphy; Florent Tintillier; Valérie Stiger-Pouvreau; Sylvain Petek (Journal of Applied Phycology, 2020)

Genetic diversity of native and introduced Phragmites (common reed) in Wisconsin - Nicholas P. Tippery; Jared D. Pesch; Brandon J. Murphy; Rachel L. Bautzmann (Genetica, 2020)

The Convergence of Cell-Based Surface Plasmon Resonance and Biomaterials: The Future of Quantifying Bio-molecular Interactions—A Review - Spencer B. Mamer; Phillip Page; Mary Murphy; Jiaojiao Wang; Pierrick Gallerne; Ali Ansari; P. I. Imoukhuede (Annals of Biomedical Engineering, 2020)

Development of a nanomedicine-loaded hydrogel for sustained delivery of an angiogenic growth factor to the ischaemic myocardium - Joanne O’Dwyer; Robert Murphy; Eimear B. Dolan; Lenka Kovarova; Martin Pravda; Vladimir Velebny; Andreas Heise; Garry P. Duffy; Sally Ann Cryan (Drug Delivery and Translational Research, 2020)

Effect of Shallow Slip Amplification Uncertainty on Probabilistic Tsunami Hazard Analysis in Subduction Zones: Use of Long-Term Balanced Stochastic Slip Models - A. Scala; S. Lorito; F. Romano; S. Murphy; J. Selva; R. Basili; A. Babeyko; A. Herrero; A. Hoechner; F. Løvholt; F. E. Maesano; P. Perfetti; et al. (Pure and Applied Geophysics, 2020)

The FluxEngine air–sea gas flux toolbox: simplified interface and extensions for in situ analyses and multiple sparingly soluble gases - Thomas Holding; Ian G. Ashton; Jamie D. Shutler; Peter E. Land; Philip D. Nightingale; Andrew P. Rees; Ian Brown; Jean-Francois Piolle; Annette Kock; Hermann W. Bange; David K. Woolf; Lonneke Goddijn-Murphy; et al. (Ocean Science, 2019)
The flow (flux) of climate-critical gases, such as carbon dioxide (CO2), between the ocean and the atmosphere is a fundamental component of our climate and an important driver of the biogeochemical systems within the oceans. Therefore, the accurate calculation of these air–sea gas fluxes is critical if we are to monitor the oceans and assess the impact that these gases are having on Earth's climate and ecosystems. FluxEngine is an open-source software toolbox that allows users to easily perform calculations of air–sea gas fluxes from model, in situ, and Earth observation data. The original development and verification of the toolbox was described in a previous publication. The toolbox has now been considerably updated to allow for its use as a Python library, to enable simplified installation, to ensure verification of its installation, to enable the handling of multiple sparingly soluble gases, and to enable the greatly expanded functionality for supporting in situ dataset analyses. This new functionality for supporting in situ analyses includes user-defined grids, time periods and projections, the ability to reanalyse in situ CO2 data to a common temperature dataset, and the ability to easily calculate gas fluxes using in situ data from drifting buoys, fixed moorings, and research cruises. Here we describe these new capabilities and demonstrate their application through illustrative case studies. The first case study demonstrates the workflow for accurately calculating CO2 fluxes using in situ data from four research cruises from the Surface Ocean CO2 ATlas (SOCAT) database. The second case study calculates air–sea CO2 fluxes using in situ data from a fixed monitoring station in the Baltic Sea. The third case study focuses on nitrous oxide (N2O) and, through a user-defined gas transfer parameterisation, identifies that biological surfactants in the North Atlantic could suppress individual N2O sea–air gas fluxes by up to 13 %. The fourth and final case study illustrates how a dissipation-based gas transfer parameterisation can be implemented and used. The updated version of the toolbox (version 3) and all documentation is now freely available.

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

Advancing our understanding of the connectivity, evolution and management of marine lobsters through genetics - Catarina N. S. Silva; Cecilia Villacorta-Rath; Laura N. Woodings; Nicholas P. Murphy; Bridget S. Green; Klaas Hartmann; Caleb Gardner; James J. Bell; Jan M. Strugnell (Reviews in Fish Biology and Fisheries, 2019)

Contrasting patterns of decline in two arboreal marsupials from Northern Australia - Alyson M. Stobo-Wilson; Brett P. Murphy; Teigan Cremona; Susan M. Carthew (Biodiversity and Conservation, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Changes in local free-living parasite populations in response to cleaner manipulation over 12 years - A. S. Grutter; S. P. Blomberg; S. Box; R. Bshary; O. Ho; E. M. P. Madin; E. C. McClure; M. G. Meekan; J. M. Murphy; M. A. Richardson; P. C. Sikkel; C. A. Sims; et al. (Oecologia, 2019)

The reduced limbed lizards of the genus Bachia (Reptilia, Squamata, Gymnophthalmidae); biogeography, cryptic diversity, and morphological convergence in the eastern Caribbean - John C. Murphy; Daniele Salvi; Joana L. Santos; Alvin L. Braswell; Stevland P. Charles; Amaél Borzée; Michael J. Jowers (Organisms Diversity & Evolution, 2019)

Staphylococcus aureus heme and siderophore-iron acquisition pathways - Brigid S. Conroy; Jason C. Grigg; Maxim Kolesnikov; L. Daniela Morales; Michael E. P. Murphy (BioMetals, 2019)

Place-making to transform urban social–ecological systems: insights from the stewardship of urban lakes in Bangalore, India - Ailbhe Murphy; Johan P. Enqvist; Maria Tengö (Sustainability Science, 2019)

Phylogeography of West Indies Coral snakes ( Micrurus ): Island colonisation and banding patterns - Michael J. Jowers; Juan Luis Garcia Mudarra; Stevland P. Charles; John C. Murphy (Zoologica Scripta, 2019)
In this study, we analyse New World coral snakes in a phylogenetic framework based upon an increased molecular data set, including novel sequences for the only two sympatric species known from an island (Trinidad, West Indies). Their presence in Trinidad and absence in Tobago offers a unique system to study the phylogeography of the region. We assess the tempo and mode of colonisation of Micrurus on the island, in addition to discussing the phylogenetic relationships for the genus Micrurus concerning two phenotypic traits, body and tail banding patterns. These relationships are analysed for the first time on statistical coalescent phylogeographic discrete ancestral reconstruction. We find a robust phylogenetic component in these characteristics, where strongly supported clades are recovered: prior to the onset of the Early Miocene, a triadal and tricolour tail clade composed of species from South America, and a second clade dating to the Middle‐Late‐ Miocene with monadal and bicolour tails widely distributed from North to South America. The divergence between clades dates to the Oligocene and suggests an ancient pre‐isthmus divergence supporting the arrival of the triadal clade into South America, before the connection between Central and South America was established. We find the two coral snakes present in the West Indies, M. diutius and M. circinalis , belong to the triadal and monadal clades, respectively. Guyana and Trinidad Micrurus diutius share the same haplotypes suggesting a Late Pleistocene–Holocene vicariance when sea level rises separated Trinidad from the mainland. A second lineage of diutius ‐like snakes is present in Guyana and is confirmed as M. lemniscatus which is assigned as a voucher and restricts the type locality for M. lemniscatus.

The existence of a fire‐mediated tree‐recruitment bottleneck in an Asian savanna - Thuy T. Nguyen; Brett P. Murphy; Patrick J. Baker (Journal of Biogeography, 2019)
Aim A considerable proportion of the global savanna biome has been mis‐classified as forest, especially in Asia. However, the structure and responses of dominant tree species to fire can help to clarify this ambiguity. Here, we examine demographic structure and fire responses of four dominant tree species in a deciduous dipterocarp forest ( DDF ) of the continental Southeast Asia. We examine whether fire creates a tree‐recruitment bottleneck in the DDF , as in savannas on other continents. Location YokDon National Park, Vietnam. Taxon Dipterocarpus tuberculatus Roxb.; Dipterocarpus obtusifolius Teysm. ex Miq.; Shorea obtusa Wall. ex Blume; Shorea siamensis (Kurz) Miq. Methods We measured the size of all 8,288 individuals of the four dominant dipterocarp species in 12 pair study sites. We then applied fire treatments (burnt or unburnt) to the plots and monitored the survival and growth of juveniles five times over the subsequent growing season. Results All four species showed clear indications of a recruitment bottleneck at the sapling stage. Almost all juveniles in the burnt plots suffered aboveground mortality, but 64% resprouted by the end of the following growing season. Compared to large juveniles, small juveniles had a significantly higher probability of aboveground mortality and a more limited ability to resprout. Within 3 months of fire, 43%–93% of individuals had resprouted, and they had recovered 67%–95% of their pre‐fire basal diameter and 43%–94% of their pre‐fire height. At the end of the post‐fire growing season, burnt juveniles experienced virtually no net increase in size; however, juveniles in unburnt plots attained up to 150% of their pre‐fire size. Main conclusions The four dominant tree species of the DDF show remarkable similarities in the demographic structures and fire‐responses with savanna tree species on other continents. Our results are consistent with the notion that the DDF is functionally similar to savannas on other continents. Fire appears to act as potent environmental filter of tree species composition in the DDF .

Circulating angiogenic cell response to sprint interval and continuous exercise - Louis O’Carroll; Bruce Wardrop; Ronan P. Murphy; Mark D. Ross; Michael Harrison (European Journal of Applied Physiology, 2019)

An injectable alginate/extra cellular matrix (ECM) hydrogel towards acellular treatment of heart failure - Clive J. Curley; Eimear B. Dolan; Matthias Otten; Svenja Hinderer; Garry P. Duffy; Bruce P. Murphy (Drug Delivery and Translational Research, 2019)

Biomass consumption by surface fires across Earth's most fire prone continent - Brett P. Murphy; Lynda D. Prior; Mark A. Cochrane; Grant J. Williamson; David M. J. S. Bowman (Global Change Biology, 2019)
Landscape fire is a key but poorly understood component of the global carbon cycle. Predicting biomass consumption by fire at large spatial scales is essential to understanding carbon dynamics and hence how fire management can reduce greenhouse gas emissions and increase ecosystem carbon storage. An Australia‐wide field‐based survey (at 113 locations) across large‐scale macroecological gradients (climate, productivity and fire regimes) enabled estimation of how biomass combustion by surface fire directly affects continental‐scale carbon budgets. In terms of biomass consumption, we found clear trade‐offs between the frequency and severity of surface fires. In temperate southern Australia, characterised by less frequent and more severe fires, biomass consumed per fire was typically very high. In contrast, surface fires in the tropical savannas of northern Australia were very frequent but less severe, with much lower consumption of biomass per fire (about a quarter of that in the far south). When biomass consumption was expressed on an annual basis, biomass consumed was far greater in the tropical savannas (>20 times that of the far south). This trade‐off is also apparent in the ratio of annual carbon consumption to net primary production ( NPP ). Across Australia's naturally vegetated land area, annual carbon consumption by surface fire is equivalent to about 11% of NPP , with a sharp contrast between temperate southern Australia (6%) and tropical northern Australia (46%). Our results emphasise that fire management to reduce greenhouse gas emissions should focus on fire prone tropical savanna landscapes, where the vast bulk of biomass consumption occurs globally. In these landscapes, grass biomass is a key driver of frequency, intensity and combustion completeness of surface fires, and management actions that increase grass biomass are likely to lead to increases in greenhouse gas emissions from savanna fires.

Outlier SNPs detect weak regional structure against a background of genetic homogeneity in the Eastern Rock Lobster, Sagmariasus verreauxi - Laura N. Woodings; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; Geoffrey W. Liggins; Bridget S. Green; Ira R. Cooke; James J. Bell; Jan M. Strugnell (Marine Biology, 2018)

Roughness effects of diatomaceous slime fouling on turbulent boundary layer hydrodynamics - Elizabeth A. K. Murphy; Julio M. Barros; Michael P. Schultz; Karen A. Flack; Cecily N. Steppe; Matthew A. Reidenbach (Biofouling, 2018)

Field of View Normalization in Multi-Site Brain MRI - Yangming Ou; Lilla Zöllei; Xiao Da; Kallirroi Retzepi; Shawn N. Murphy; Elizabeth R. Gerstner; Bruce R. Rosen; P. Ellen Grant; Jayashree Kalpathy-Cramer; Randy L. Gollub (Neuroinformatics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

High-definition infrared thermography of ice nucleation and propagation in wheat under natural frost conditions and controlled freezing - David P. Livingston; Tan D. Tuong; J. Paul Murphy; Lawrence V. Gusta; Ian Willick; Micheal E. Wisniewski (Planta, 2018)

Temporal genetic patterns of diversity and structure evidence chaotic genetic patchiness in a spiny lobster - Cecilia Villacorta‐Rath; Carla A. Souza; Nicholas P. Murphy; Bridget S. Green; Caleb Gardner; Jan M. Strugnell (Molecular Ecology, 2018)
Population structure of many marine organisms is spatially patchy and varies within and between years, a phenomenon defined as chaotic genetic patchiness. This results from the combination of planktonic larval dispersal and environmental stochasticity. Additionally, in species with bi‐partite life, postsettlement selection can magnify these genetic differences. The high fecundity (up to 500,000 eggs annually) and protracted larval duration (12–24 months) and dispersal of the southern rock lobster, Jasus edwardsii , make it a good test species for chaotic genetic patchiness and selection during early benthic life. Here, we used double digest restriction site‐associated DNA sequencing (dd RAD seq) to investigate chaotic genetic patchiness and postsettlement selection in this species. We assessed differences in genetic structure and diversity of recently settled pueruli across four settlement years and between two sites in southeast Australia separated by approximately 1,000 km. Postsettlement selection was investigated by identifying loci under putative positive selection between recently settled pueruli and postpueruli and quantifying differences in the magnitude and strength of the selection at each year and site. Genetic differences within and among sites through time in neutral SNP markers indicated chaotic genetic patchiness. Recently settled puerulus at the southernmost site exhibited lower genetic diversity during years of low puerulus catches, further supporting this hypothesis. Finally, analyses of outlier SNP s detected fluctuations in the magnitude and strength of the markers putatively under positive selection over space and time. One locus under putative positive selection was consistent at both locations during the same years, suggesting the existence of weak postsettlement selection.

Glucuronide and Sulfate Conjugates of Bisphenol A: Chemical Synthesis and Correlation Between Their Urinary Levels and Plasma Bisphenol A Content in Voluntary Human Donors - Ka-Lok Ho; Ka-Ki Yuen; Man-Shan Yau; Margaret B. Murphy; Yi Wan; Bonnie M.-W. Fong; Sidney Tam; John P. Giesy; Kelvin S.-Y. Leung; Michael H.-W. Lam (Archives of Environmental Contamination and Toxicology, 2017)

A Synergistic Approach for Evaluating Climate Model Output for Ecological Applications - Rachel D. Cavanagh; Eugene J. Murphy; Thomas J. Bracegirdle; John Turner; Cheryl A. Knowland; Stuart P. Corney; Walker O. Smith; Claire M. Waluda; Nadine M. Johnston; Richard G. J. Bellerby; Andrew J. Constable; Daniel P. Costa; et al. (Frontiers in Marine Science, 2017)

Nitrogen availability alters rhizosphere processes mediating soil organic matter mineralisation - Conor J. Murphy; Elizabeth M. Baggs; Nicholas Morley; David P. Wall; Eric Paterson (Plant and Soil, 2017)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.

Does inherent flammability of grass and litter fuels contribute to continental patterns of landscape fire activity? - Lynda D. Prior; Brett P. Murphy; Grant J. Williamson; Mark A. Cochrane; W. Matt Jolly; David M. J. S. Bowman (Journal of Biogeography, 2017)
Aims To (1) identify the trade‐offs among flammability attributes within grass and litter fuel types; (2) determine how flammability attributes of grass and litter fuels vary across macro‐ecological gradients; and (3) test our hypothesis that inherent flammability attributes of grass and litter fuels scale to satellite‐derived proxies for fire frequency and intensity. Location Continent of Australia. Methods Samples of litter and grass fuels collected from 133 sites across Australia were oven dried, then burnt under controlled conditions. Measurements of ignitability, combustibility and sustainability were made. Estimates of fire frequency and fire radiative power (a proxy for intensity) were derived from satellite imagery. Multivariate analyses were used to identify inter‐relationships among variables and trends across macro‐ecological gradients. Results Flammability was best described by two axes: high rate of combustion versus long duration of burning, and fast rate of spread versus high maximum temperature. As expected, our study confirmed that grass and litter fuel types have inherently differently flammability attributes whereby grass samples burn more quickly, with a higher rate of spread, than litter samples. However, there were also smaller differences in flammability attributes within fuel types, which scaled to rainfall, temperature and soil phosphorus concentrations. In keeping with our hypothesis, we found correlations between inherent fuel flammability attributes and landscape fire activity across the Australian continent. Fire frequency and rate of combustion of grass fuels were both highest in the tropics, and fire intensity and maximum temperature during combustion of litter fuels were highest in temperate areas. Main conclusions At a continental scale, we found landscape fire activity was correlated with inherent flammability of grass and litter fuels. This inherent flammability contributes to observed pyrogeographical patterns that are shaped by climate through its known effects on plant productivity, the abundance of cured grass biomass and fire weather.

Evaluation of the BioFire FilmArray® GastrointestinalPanel in a Midwestern Academic Hospital - C. N. Murphy; R. C. Fowler; P. C. Iwen; P. D. Fey (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

A theoretical examination of environmental effects on the life cycle schedule and range limits of the invasive seaweed Undaria pinnatifida - James T. Murphy; Mark P. Johnson; Frédérique Viard (Biological Invasions, 2017)

Savanna woody encroachment is widespread across three continents - Nicola Stevens; Caroline E. R. Lehmann; Brett P. Murphy; Giselda Durigan (Global Change Biology, 2017)
Tropical savannas are a globally extensive biome prone to rapid vegetation change in response to changing environmental conditions. Via a meta‐analysis, we quantified savanna woody vegetation change spanning the last century. We found a global trend of woody encroachment that was established prior the 1980s. However, there is critical regional variation in the magnitude of encroachment. Woody cover is increasing most rapidly in the remaining uncleared savannas of South America, most likely due to fire suppression and land fragmentation. In contrast, Australia has experienced low rates of encroachment. When accounting for land use, African savannas have a mean rate annual woody cover increase two and a half times that of Australian savannas. In Africa, encroachment occurs across multiple land uses and is accelerating over time. In Africa and Australia, rising atmospheric CO 2 , changing land management and rainfall are likely causes. We argue that the functional traits of each woody flora, specifically the N‐fixing ability and architecture of woody plants, are critical to predicting encroachment over the next century and that African savannas are at high risk of widespread vegetation change.

Pilot Trial of Intravenous Lipid Emulsion Treatment for Severe Nifedipine-Induced Shock - Christine M. Murphy; Cliff Williams; Michael E. Quinn; Brian Nicholson; Thomas Shoe; Michael C. Beuhler; William P. Kerns (Journal of Medical Toxicology, 2016)

Reexamining Chronic Toxoplasma gondii Infection: Surprising Activity for a “Dormant” Parasite - Anthony P. Sinai; Elizabeth A. Watts; Animesh Dhara; Robert D. Murphy; Matthew S. Gentry; Abhijit Patwardhan (Current Clinical Microbiology Reports, 2016)

Outlier SNPs enable food traceability of the southern rock lobster, Jasus edwardsii - Cecilia Villacorta-Rath; Irina Ilyushkina; Jan M. Strugnell; Bridget S. Green; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; James J. Bell (Marine Biology, 2016)

The relative importance of intrinsic and extrinsic factors in the decline of obligate seeder forests - David M. J. S. Bowman; Grant J. Williamson; Lynda D. Prior; Brett P. Murphy (Global Ecology and Biogeography, 2016)
Forests that regenerate exclusively from seed following high‐severity fire are particularly vulnerable to local extinction if fire frequency leaves insufficient time for regenerating plants to reach sexual maturity. We evaluate the relative importance of extrinsic (such as fire weather and climate cycles) and intrinsic (such as proneness to fire due to stand age and structural development) factors in driving the decline of obligate seeder forests. We illustrate this using obligate seeding alpine ash ( Eucalyptus delegatensis ) forests in the montane regions of Victoria, Australia, that were burnt by megafires in 2003 (142,256 ha) or 2007 (79,902 ha), including some twice‐burnt areas (11,599 ha). Geospatial analyses showed only a small effect of stand age on the remote sensing estimates of crown defoliation, but a substantial effect of forest fire weather, as measured by forest fire danger index (FFDI). Analysis of meteorological data over the last century showed that 5‐year increases in FFDI precede cycle major fires in the E. delegatensis forests. Such strong extrinsic climate/weather driving of high‐severity fires is consistent with the ‘interval squeeze model’ that postulates the vulnerability of obligate seeder forests to landscape‐scale demographic collapse in response to worsening fire weather under climate change.

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Erratum to: New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

The Jebel Ohier deposit—a newly discovered porphyry copper–gold system in the Neoproterozoic Arabian–Nubian Shield, Red Sea Hills, NE Sudan - F. P. Bierlein; S. McKeag; N. Reynolds; C. J. Bargmann; W. Bullen; F. C. Murphy; H. Al-Athbah; C. Brauhart; W. Potma; S. Meffre; S. McKnight (Mineralium Deposita, 2016)

Chronic methamphetamine exposure prior to middle cerebral artery occlusion increases infarct volume and worsens cognitive injury in Male mice - Damian G. Zuloaga; Jianming Wang; Sydney Weber; Gregory P. Mark; Stephanie J. Murphy; Jacob Raber (Metabolic Brain Disease, 2016)

Human-Imposed, Fine-Grained Patch Burning Explains the Population Stability of a Fire-Sensitive Conifer in a Frequently Burnt Northern Australia Savanna - Clay Trauernicht; Brett P. Murphy; Lynda D. Prior; Michael J. Lawes; David M. J. S. Bowman (Ecosystems, 2016)

Impact of including land-use change emissions from biofuels on meeting GHG emissions reduction targets: the example of Ireland - Magdalena M. Czyrnek-Delêtre; Alessandro Chiodi; Jerry D. Murphy; Brian P. Ó Gallachóir (Clean Technologies and Environmental Policy, 2016)

Changes in Dopamine Signalling Do Not Underlie Aberrant Hippocampal Plasticity in a Mouse Model of Huntington’s Disease - Glenn M. Dallérac; Damian M. Cummings; Mark C. Hirst; Austen J. Milnerwood; Kerry P. S. J. Murphy (NeuroMolecular Medicine, 2016)

Pattern, prediction and parsimony in continental‐scale synthesis of pyromes: a reply to Gosper et al . - Brett P. Murphy; Michael J. Lawes; David M.J.S. Bowman (Journal of Biogeography, 2016)
We (Murphy et al ., 2013; Clarke et al ., 2015) have recently developed a framework to understand the spatial distribution of fire regimes and plant fire‐response traits at large spatial scales. We integrated a range of data sources to create a continental‐scale overview of Australian pyromes from which to infer pyrogeographic drivers. Gosper et al . (in press) have criticized our approach, based on our misclassification of a vegetation type (eucalypt woodland), with distinct fire regime, in the Coolgardie bioregion of Western Australia. We argue that the intention of our integrative approach was to develop and refine conceptual models of Australian pyrogeography, not to produce a predictive map of fire regimes, and certainly not to guide local‐scale fire management. Like all models, continental‐scale syntheses of pyromes are imperfect, yet they still represent powerful tools for understanding the drivers of the spatial distribution of fire regimes.

Farm gate level nitrogen balance and use efficiency changes post implementation of the EU Nitrates Directive - Cathal Buckley; David P. Wall; Brian Moran; Stephen O’Neill; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2016)

Desert spring refugia: museums of diversity or evolutionary cradles? - Nicholas P. Murphy; Michelle T. Guzik; Steven J. B. Cooper; Andrew D. Austin (Zoologica Scripta, 2015)
Refugia play a critical role in preserving species unable to move or adapt to cope with environmental change. The role of refugia as ‘museums of diversity’ means these environments have a high conservation priority. Less well known, however, is the role that isolated and fragmented refugia can play in the generation of new diversity. Here, we examined the diversification and evolutionary history of a community of endemic invertebrates that inhabit Australian desert spring refugia. We compared the phylogenies of seven endemic groups ( Haloniscus and Phreatomerus isopods, chiltoniid amphipods, Ngarawa ostracods, Trochidrobia and Fonscochlea snails and Gymnochthebius beetles) from these springs and examine the rates and timing of diversification and reconstructed the phylogeographic history of each taxon. Despite major life‐history differences among these taxa, they demonstrate remarkable similarities in their evolutionary histories. All groups have multiple lineages that extend back to a time before the formation of present‐day deserts, and significant geographic‐based diversification since adapting to a refugial habitat. The results provide further evidence that refugia act as museums of biodiversity, preserving lineages that would have otherwise gone extinct. However, we also observed that isolation in refugia corresponds with significant diversification, leading to a recently evolved, novel endemic fauna, supporting the idea that fragmented refugia provide ideal conditions for the generation of future biodiversity hotspots.

Evaluation of Cartilage Repair by Mesenchymal Stem Cells Seeded on a PEOT/PBT Scaffold in an Osteochondral Defect - V. Barron; K. Merghani; G. Shaw; C. M. Coleman; J. S. Hayes; S. Ansboro; A. Manian; G. O’Malley; E. Connolly; A. Nandakumar; C. A. van Blitterswijk; P. Habibovic; et al. (Annals of Biomedical Engineering, 2015)

Regional population differentiation in the morphologically diverse, elevationally widespread Nearctic skipper Polites sabuleti - Joshua P. Jahner; Matthew L. Forister; Chris C. Nice; James A. Fordyce; Joseph S. Wilson; Dennis D. Murphy; Zachary H. Marion; Arthur M. Shapiro (Journal of Biogeography, 2015)
Aim To evaluate three phylogeographical models associated with the presence of mountains (montane vicariance, sky island and parapatry) as drivers of intraspecific diversification in the sandhill skipper, Polites sabuleti (Lepidoptera: Hesperiidae), a morphologically variable species found in a variety of habitats from sea level to the alpine zone. Location Western North America. Methods The mitochondrial cytochrome c oxidase subunit II region was sequenced in 189 P. sabuleti individuals. Mitochondrial sequences were used in a spatial analysis of molecular variance ( SAMOVA ) to evaluate geographical population structure. AFLP markers were also generated for 347 individuals in order to estimate admixture proportions and examine population differentiation based on the nuclear genome. Results Twenty‐five mitochondrial haplotypes and 42 anonymous AFLP loci were found across 36 collection localities. Mitochondrial variation suggests a degree of regional population structure, although at least one of the inferred population groups extends over nearly the entire geographical range of the species. Analyses of nuclear data ( AFLP s) identified five genetic clusters, including one restricted to high elevations in the Sierra Nevada. Main conclusions The distribution of genetic variation within Polites sabuleti , a species with a broad elevational range, does not strictly support either mountain‐associated vicariance or ‘sky island’ isolation as the dominant process. Instead, we find complex population structure, including evidence for divergence between high‐ and low‐elevation populations in the Sierra Nevada mountains.

The OceanFlux Greenhouse Gases methodology for deriving a sea surface climatology of CO 2 fugacity in support of air–sea gas flux studies - L. M. Goddijn-Murphy; D. K. Woolf; P. E. Land; J. D. Shutler; C. Donlon (Ocean Science, 2015)
Climatologies, or long-term averages, of essential climate variables are useful for evaluating models and providing a baseline for studying anomalies. The Surface Ocean CO2 Atlas (SOCAT) has made millions of global underway sea surface measurements of CO2 publicly available, all in a uniform format and presented as fugacity, fCO2. As fCO2 is highly sensitive to temperature, the measurements are only valid for the instantaneous sea surface temperature (SST) that is measured concurrently with the in-water CO2 measurement. To create a climatology of fCO2 data suitable for calculating air–sea CO2 fluxes, it is therefore desirable to calculate fCO2 valid for a more consistent and averaged SST. This paper presents the OceanFlux Greenhouse Gases methodology for creating such a climatology. We recomputed SOCAT's fCO2 values for their respective measurement month and year using monthly composite SST data on a 1° × 1° grid from satellite Earth observation and then extrapolated the resulting fCO2 values to reference year 2010. The data were then spatially interpolated onto a 1° × 1° grid of the global oceans to produce 12 monthly fCO2 distributions for 2010, including the prediction errors of fCO2 produced by the spatial interpolation technique. The partial pressure of CO2 (pCO2) is also provided for those who prefer to use pCO2. The CO2 concentration difference between ocean and atmosphere is the thermodynamic driving force of the air–sea CO2 flux, and hence the presented fCO2 distributions can be used in air–sea gas flux calculations together with climatologies of other climate variables.

Developing the EU Farm Accountancy Data Network to derive indicators around the sustainable use of nitrogen and phosphorus at farm level - Cathal Buckley; David P. Wall; Brian Moran; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2015)

Improving estimates of tropical peatland area, carbon storage, and greenhouse gas fluxes - I. T. Lawson; T. J. Kelly; P. Aplin; A. Boom; G. Dargie; F. C. H. Draper; P. N. Z. B. P. Hassan; J. Hoyos-Santillan; J. Kaduk; D. Large; W. Murphy; S. E. Page; et al. (Wetlands Ecology and Management, 2015)

Mcl-1 is vital for neutrophil survival - Mark P. Murphy; Emma Caraher (Immunologic Research, 2015)

Investigation of the mechanisms mediating MDMA “Ecstasy”-induced increases in cerebro-cortical perfusion determined by btASL MRI - J Rouine; M. E. Kelly; C. Jennings-Murphy; P. Duffy; I. Gorman; S. Gormley; C. M. Kerskens; Andrew Harkin (Psychopharmacology, 2015)

Community structure and palaeoecological implications of calcareous encrusters on artificial substrates across a Mexican Caribbean reef - L. J. Hepburn; P. Blanchon; G. Murphy; L. Cousins; C. T. Perry (Coral Reefs, 2015)

Groundwater Protection, Risk Awareness, Knowledge Transfer and Public Health: The Role of “Future Custodians” - P. D. Hynds; H. M. Murphy; I. Kelly; U. Fallon (Water Resources Management, 2014)

Common vitamin D pathway gene variants reveal contrasting effects on serum vitamin D levels in African Americans and European Americans - Ken Batai; Adam B. Murphy; Ebony Shah; Maria Ruden; Jennifer Newsome; Sara Agate; Michael A. Dixon; Hua Yun Chen; Leslie A. Deane; Courtney M. P. Hollowell; Chiledum Ahaghotu; Rick A. Kittles (Human Genetics, 2014)

Improving the power of genetic association tests with imperfect phenotype derived from electronic medical records - Jennifer A. Sinnott; Wei Dai; Katherine P. Liao; Stanley Y. Shaw; Ashwin N. Ananthakrishnan; Vivian S. Gainer; Elizabeth W. Karlson; Susanne Churchill; Peter Szolovits; Shawn Murphy; Isaac Kohane; Robert Plenge; et al. (Human Genetics, 2014)

An Experimental Investigation of the Effect of Mechanical and Biochemical Stimuli on Cell Migration Within a Decellularized Vascular Construct - William S. Sheridan; Alan J. Ryan; Garry P. Duffy; Fergal J. O’Brien; Bruce P. Murphy (Annals of Biomedical Engineering, 2014)

Life history of harbor porpoises ( Phocoena phocoena ) in Scottish ( UK ) waters - Jennifer A. Learmonth; Sinead Murphy; Patricia L. Luque; Robert J. Reid; I. Anthony P. Patterson; Andrew Brownlow; Harry M. Ross; Jason P. Barley; M. Begoña Santos; Graham J. Pierce (Marine Mammal Science, 2014)
Life history parameters were determined for stranded and bycaught harbor porpoises ( Phocoena phocoena ) from Scottish ( UK ) waters (1992–2005). Fetal growth rate was 84.4 mm/mo and mean size at birth was 76.4 cm (range 65–88 cm). Males and females had a similar range of body lengths (65–170 cm and 66–173 cm, respectively), although asymptotic lengths were higher in females than males (approximately 158 cm and 147 cm, respectively). Nonpregnant females were significantly lighter, in relation to their length than males. Maximum estimated age was 20 yr for both sexes. Age at sexual maturity ( ASM ) was estimated as 4.35 yr in females and 5.00 yr in males. Conception occurred mainly in July and August although reproductively active males were recorded during April to July. Gestation lasted 10–11 mo, with calving mainly between May and July. Lactating females were recorded during June to November, while small calves with solid food in their stomachs were found mainly during February to May. Estimated pregnancy rate (0.34–0.40) is lower than recorded elsewhere, but is likely underestimated due to the prevalence of mature females of poor health status in the sample. Nevertheless, cetacean strandings can be an essential source of data on demographic parameters.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

There is a critical weight range for A ustralia's declining tropical mammals - Brett P. Murphy; Hugh F. Davies (Global Ecology and Biogeography, 2014)
Many mammals in A ustralia's tropical north are in severe decline, yet understanding of the drivers of this decline is remarkably limited. Recently, F isher et al . ( Global Ecology and Biogeography , 2014, 23 , 181−190) examined the traits that are associated with declining marsupial species in northern A ustralia. They concluded that, in this region, declines are most pronounced in the smallest species (those with the lowest body mass). This is in strong contrast to the significant declines that occurred earlier in central and southern A ustralia before the mid 20th century, which were most pronounced in medium‐sized species, the so‐called ‘critical weight range’ (35−5500 g). Here we show that F isher et al . have misinterpreted their dataset; in northern A ustralia, the pattern of mammal decline in relation to body mass is remarkably similar to that in central and southern A ustralia, with mammal decline strongly concentrated in the critical weight range, suggesting fundamentally similar drivers between north and south.

Variability in size-selective mortality obscures the importance of larval traits to recruitment success in a temperate marine fish - Hannah M. Murphy; Fletcher W. Warren-Myers; Gregory P. Jenkins; Paul A. Hamer; Stephen E. Swearer (Oecologia, 2014)

3D ground model development for an active landslide in Lias mudrocks using geophysical, remote sensing and geotechnical methods - A. J. Merritt; J. E. Chambers; W. Murphy; P. B. Wilkinson; L. J. West; D. A. Gunn; P. I. Meldrum; M. Kirkham; N. Dixon (Landslides, 2014)

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

Pyrogeographic models, feedbacks and the future of global fire regimes - David M. J. S. Bowman; Brett P. Murphy; Grant J. Williamson; Mark A. Cochrane (Global Ecology and Biogeography, 2014)
Conceptual and phenomenological macroecological models of current global fire activity have demonstrated the overwhelming control exerted by primary productivity. Fire activity is very high in savanna regions with intermediate primary productivity, and very low in both densely forested regions with high productivity and arid/cold regions with low productivity. However, predicting future global fire activity using such macroecological models of fire's global ‘niche’ may not be possible because of the feedbacks between fire, climate and vegetation that underpin the fire−productivity relationship. Improving forecasts of global fire activity demands the use of dynamic models to determine how climate, CO 2 , vegetation (i.e. canopy closure and plant functional types) and primary productivity constrain fire and evaluation of the strength of feedbacks amongst these variables.

Modulation of Mcl-1 sensitizes glioblastoma to TRAIL-induced apoptosis - Á. C. Murphy; B. Weyhenmeyer; J. Noonan; S. M. Kilbride; S. Schimansky; K. P. Loh; D. Kögel; A. G. Letai; J. H. M. Prehn; B. M. Murphy (Apoptosis, 2014)

Abrupt fire regime change may cause landscape‐wide loss of mature obligate seeder forests - David M. J. S. Bowman; Brett P. Murphy; Dominic L. J. Neyland; Grant J. Williamson; Lynda D. Prior (Global Change Biology, 2014)
Obligate seeder trees requiring high‐severity fires to regenerate may be vulnerable to population collapse if fire frequency increases abruptly. We tested this proposition using a long‐lived obligate seeding forest tree, alpine ash ( Eucalyptus delegatensis ), in the Australian Alps. Since 2002, 85% of the Alps bioregion has been burnt by several very large fires, tracking the regional trend of more frequent extreme fire weather. High‐severity fires removed 25% of aboveground tree biomass, and switched fuel arrays from low loads of herbaceous and litter fuels to high loads of flammable shrubs and juvenile trees, priming regenerating stands for subsequent fires. Single high‐severity fires caused adult mortality and triggered mass regeneration, but a second fire in quick succession killed 97% of the regenerating alpine ash. Our results indicate that without interventions to reduce fire severity, interactions between flammability of regenerating stands and increased extreme fire weather will eliminate much of the remaining mature alpine ash forest.

Climatological analysis of December rainfall in the Panama Canal Watershed - Michael J. Murphy; Konstantine P. Georgakakos; Eylon Shamir (International Journal of Climatology, 2014)
Monthly accumulated precipitation over the tropical Panama Canal Watershed has the largest interannual variability in December, with the wettest month on record being December 2010. December accumulated precipitation over the watershed is found to vary with sea surface temperature ( SST ) anomalies in both the tropical North Atlantic and equatorial Pacific oceans, but a considerably stronger relationship is found with the difference between these SST anomalies. The configuration of SST anomalies in these two ocean basins during December has a strong effect on the flux of low‐level moisture over the Caribbean Sea, southern Central America, and the eastern Pacific Ocean through the modification of the Caribbean Low‐Level Jet ( CLLJ ) and the Chorro del Occidente Colombiano ( CHOCO ) jet. Wet Decembers in the watershed are associated with cool (warm) SST anomalies in the tropical Pacific (North Atlantic), a weakening (strengthening) of the CLLJ ( CHOCO jet), and increased moisture convergence over and around Panama, with the opposite conditions associated with dry Decembers. The SST anomalies in these two ocean basins affect the distribution of daily precipitation during December differently, with SST anomalies in the Pacific (Atlantic) predominately associated with changes in the frequency of heavier (lighter) precipitation. The analysis shows that December 2010 followed the pattern of associations of wet Decembers but with the highest intensity of precipitation and CHOCO jet strength.

Fire regimes and woody biomass dynamics in Australian savannas - Brett P. Murphy; Caroline E. R. Lehmann; Jeremy Russell‐Smith; Michael J. Lawes (Journal of Biogeography, 2014)
Aim Many tropical savannas are undergoing a trend of increasing woody biomass, or ‘woody thickening’. Management to reduce fire frequency and intensity in savannas could substantially increase the amount of carbon stored in woody biomass. We addressed two questions: (1) are northern Australian savannas thickening; and (2) to what extent, and by what demographic processes, does fire affect woody biomass accumulation? Location Three large national parks, covering 24,000 km 2 , in monsoonal northern Australia. Methods We examined changes in woody biomass carbon stocks – inferred from tree basal area and the density of woody understorey plants – over a 10‐year period in 136 savanna monitoring plots. We statistically assessed these changes in relation to fire frequency and severity. We used a meta‐analysis to identify general trends in woody cover in Australian savannas over the last half‐century. Results Woody biomass carbon stocks were relatively stable across the three national parks, but rates of change were statistically indistinguishable from earlier findings of a weak thickening trend. Change was negatively correlated with fire frequency, particularly the frequency of severe fires. High frequencies of severe fires decreased rates of accumulation of biomass by existing trees (through reductions in tree growth and death of individual stems), rather than whole‐tree mortality and suppression of recruitment. However, across northern Australia, our meta‐analysis identified a general, albeit weak, trend of woody thickening. Main conclusions The drivers of northern Australia's weak thickening trend are uncertain, but likely candidates include increasing atmospheric CO 2 concentration and water availability, and pastoral intensification. We demonstrate that changes to fire management have the potential to either increase or decrease rates of woody thickening relative to any underlying trend. Understanding how savanna fires affect woody biomass, and how fire effects are mediated by climate and CO 2 , are essential research priorities to predict the fate of savannas.

Decreased consumption of sweet fluids in mu opioid receptor knockout mice: a microstructural analysis of licking behavior - Sean B. Ostlund; Alisa Kosheleff; Nigel T. Maidment; Niall P. Murphy (Psychopharmacology, 2013)

Molecular cloning of the trypsin inhibitor from the skin secretion of the Madagascan Tomato Frog, Dyscophus guineti (Microhylidae), and insights into its potential defensive role - Enrico König; Christina Wesse; Anna C. Murphy; Mei Zhou; Lei Wang; Tianbao Chen; Chris Shaw; Olaf R. P. Bininda-Emonds (Organisms Diversity & Evolution, 2013)

Evaluation of real-time flash flood forecasts for Haiti during the passage of Hurricane Tomas, November 4–6, 2010 - E. Shamir; K. P. Georgakakos; C. Spencer; T. M. Modrick; M. J. Murphy; R. Jubach (Natural Hazards, 2013)

Fire regimes of A ustralia: a pyrogeographic model system - Brett P. Murphy; Ross A. Bradstock; Matthias M. Boer; John Carter; Geoffrey J. Cary; Mark A. Cochrane; Roderick J. Fensham; Jeremy Russell‐Smith; Grant J. Williamson; David M. J. S. Bowman (Journal of Biogeography, 2013)
Aim Comparative analyses of fire regimes at large geographical scales can potentially identify ecological and climatic controls of fire. Here we describe A ustralia's broad fire regimes, and explore interrelationships and trade‐offs between fire regime components. We postulate that fire regime patterns will be governed by trade‐offs between moisture, productivity, fire frequency and fire intensity. Location Australia. Methods We reclassified a vegetation map of A ustralia, defining classes based on typical fuel and fire types. Classes were intersected with a climate classification to derive a map of ‘fire regime niches’. Using expert elicitation and a literature search, we validated each niche and characterized typical and extreme fire intensities and return intervals. Satellite‐derived active fire detections were used to determine seasonal patterns of fire activity. Results Fire regime characteristics are closely related to the latitudinal gradient in summer monsoon activity. Frequent low‐intensity fires occur in the monsoonal north, and infrequent, high‐intensity fires in the temperate south, demonstrating a trade‐off between frequency and intensity: that is, very high‐intensity fires are only associated with very low‐frequency fire regimes in the high biomass eucalypt forests of southern A ustralia. While these forests occasionally experience extremely intense fires (> 50,000 kW m −1 ), such regimes are exceptional, with most of the continent dominated by grass fuels, typically burning with lower intensity ( −1 ). Main conclusions Australia's fire regimes exhibit a coherent pattern of frequent, grass‐fuelled fires in many differing vegetation types. While eucalypts are a quintessential A ustralian entity, their contribution as a dominant driver of high‐intensity fire regimes, via their litter and bark fuels, is restricted to the forests of the continent's southern and eastern extremities. Our analysis suggests that the foremost driver of fire regimes at the continental scale is not productivity, as postulated conceptually, but the latitudinal gradient in summer monsoon rainfall activity.

Virus species polemics: 14 senior virologists oppose a proposed change to the ICTV definition of virus species - Marc H. V. Van Regenmortel; Hans-Wolfgang Ackermann; Charles H. Calisher; Ralf G. Dietzgen; Marian C. Horzinek; Gunther M. Keil; Brian W. J. Mahy; Giovanni P. Martelli; Frederick A. Murphy; Craig Pringle; Bert K. Rima; Tim Skern; et al. (Archives of Virology, 2013)

A Strategy for Prioritizing Threats and Recovery Actions for At-Risk Species - Catherine R. Darst; Philip J. Murphy; Nathan W. Strout; Steven P. Campbell; Kimberleigh J. Field; Linda Allison; Roy C. Averill-Murray (Environmental Management, 2013)

Increased caveolae density and caveolin-1 expression accompany impaired NO-mediated vasorelaxation in diet-induced obesity - T. Hilton Grayson; Preet S. Chadha; Paul P. Bertrand; Hui Chen; Margaret J. Morris; Sevvandi Senadheera; Timothy V. Murphy; Shaun L. Sandow (Histochemistry and Cell Biology, 2013)

Current evidence for human yersiniosis in Ireland - T. Ringwood; B. P. Murphy; N. Drummond; J. F. Buckley; A. P. Coveney; H. P. Redmond; J. P. Power; S. Fanning; M. B. Prentice (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Non-steroidal anti-inflammatory drug use and ovarian cancer risk: findings from the NIH-AARP Diet and Health Study and systematic review - Megan A. Murphy; Britton Trabert; Hannah P. Yang; Yikyung Park; Louise A. Brinton; Patricia Hartge; Mark E. Sherman; Albert Hollenbeck; Nicolas Wentzensen (Cancer Causes & Control, 2012)

Erratum to: Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Estimating rates of biologically driven coral reef framework production and erosion: a new census-based carbonate budget methodology and applications to the reefs of Bonaire - C. T. Perry; E. N. Edinger; P. S. Kench; G. N. Murphy; S. G. Smithers; R. S. Steneck; P. J. Mumby (Coral Reefs, 2012)

Trapped in desert springs: phylogeography of Australian desert spring snails - Nicholas P. Murphy; Martin F. Breed; Michelle T. Guzik; Steven J. B. Cooper; Andrew D. Austin (Journal of Biogeography, 2012)
Aim We investigate the phylogeographical history and determine the time‐scale of population divergence of hydrobiid freshwater snails (genus Trochidrobia ) inhabiting groundwater springs in the Australian desert. We test the hypothesis that divergence between geographically distinct snail populations occurred simultaneously due to their isolation in hydrologically discrete spring systems, i.e. ‘trapped in desert springs’. Location Groundwater springs of the Great Artesian Basin (GAB) in central Australia. Methods DNA sequence data from the mitochondrial cytochrome c oxidase subunit I gene and the nuclear 28S and internal transcribed spacer rRNA genes were used to reconstruct phylogenetic relationships within and among three species of Trochidrobia (Hydrobiidae): T. punicea (13 spring groups, n = 90) , T. smithi (12 spring groups, n = 62) and T. minuta (2 spring groups, n = 4). Bayesian relaxed molecular clock analyses and approximate Bayesian computation were used to date lineage divergence and distinguish between alternative biogeographical scenarios. Results The diversification of the three Trochidrobia species probably occurred between 2.54 and 9.3 Ma, prior to the formation of the springs c . 1 Ma. Intraspecific divergences within the two widespread species occurred after the formation and colonization of the springs. Coalescent modelling and molecular clock analyses supported a simultaneous radiation of five allopatric intraspecific snail lineages within T. punicea (two lineages) and T. smithi (three lineages) across the GAB springs examined. Main conclusions The analyses support the ‘trapped in desert springs’ hypothesis for the diversification of intraspecific lineages within the species T. punicea and T. smithi . This hypothesis suggests that the formation of deserts around Lake Eyre in the early Pleistocene led to the hydrological isolation of spring complexes in the GAB, resulting in significant molecular divergence, but no morphological divergence, of Trochidrobia snail populations.

Within-season dynamics of red palm mite (Raoiella indica) and phytoseiid predators on two host palm species in south-west India - B. Taylor; P. M. Rahman; S. T. Murphy; V. V. Sudheendrakumar (Experimental and Applied Acarology, 2012)

Isolating early cortical generators of visual-evoked activity: a systems identification approach - Jeremy W. Murphy; Simon P. Kelly; John J. Foxe; Edmund C. Lalor (Experimental Brain Research, 2012)

What controls the distribution of tropical forest and savanna? - Brett P. Murphy; David M.J.S. Bowman (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 748–758 Abstract Forest and savanna biomes dominate the tropics, yet factors controlling their distribution remain poorly understood. Climate is clearly important, but extensive savannas in some high rainfall areas suggest a decoupling of climate and vegetation. In some situations edaphic factors are important, with forest often associated with high nutrient availability. Fire also plays a key role in limiting forest, with fire exclusion often causing a switch from savanna to forest. These observations can be captured by a broad conceptual model with two components: (1) forest and savanna are alternative stable states, maintained by tree cover‐fire feedbacks, (2) the interaction between tree growth rates and fire frequency limits forest development; any factor that increases growth (e.g. elevated availability of water, nutrients, CO 2 ), or decreases fire frequency, will favour canopy closure. This model is consistent with the range of environmental variables correlated with forest distribution, and with the current trend of forest expansion, likely driven by increasing CO 2 concentrations. Resolving the drivers of forest and savanna distribution has moved beyond simple correlative studies that are unlikely to establish ultimate causation. Experiments using Dynamic Global Vegetation Models, parameterised with measurements from each continent, provide an important tool for understanding the controls of these systems.

Association of cord blood methylation fractions at imprinted insulin-like growth factor 2 (IGF2), plasma IGF2, and birth weight - Cathrine Hoyo; Kimberly Fortner; Amy P. Murtha; Joellen M. Schildkraut; Adelheid Soubry; Wendy Demark-Wahnefried; Randy L. Jirtle; Joanne Kurtzberg; Michele R. Forman; Francine Overcash; Zhiqing Huang; Susan K. Murphy (Cancer Causes & Control, 2012)

Advancing the use of minirhizotrons in wetlands - C. M. Iversen; M. T. Murphy; M. F. Allen; J. Childs; D. M. Eissenstat; E. A. Lilleskov; T. M. Sarjala; V. L. Sloan; P. F. Sullivan (Plant and Soil, 2012)

Rapid Biomass Quality Determination of Corn Stover Using Near-Infrared Reflectance Spectroscopy - Patrick T. Murphy; Kenneth J. Moore; D. Raj Raman; Robert P. Anex; Steven L. Fales (BioEnergy Research, 2012)

Did central Australian megafaunal extinction coincide with abrupt ecosystem collapse or gradual climate change? - Brett P. Murphy; Grant J. Williamson; David M. J. S. Bowman (Global Ecology and Biogeography, 2012)
Aim In central Australia, the giant flightless bird Genyornis newtoni disappeared about 45–50 thousand years ago (ka). It has been reported that coincident with this extinction the carbon isotopic composition of preserved eggshells of the extant emu ( Dromaius novaehollandiae ) shows an abrupt dietary shift from tropical grasses (C 4 photosynthesis) to temperate grasses and/or woody browse (C 3 photosynthesis). This abrupt shift has been interpreted as signalling ‘ecosystem collapse’ due to landscape burning by humans. We evaluate an alternative interpretation, that the shift in diet was not abrupt, but gradual, and caused by the weakening of the Australian monsoon. Location Lake Eyre, central Australia. Methods We re‐analysed a large, published dataset of emu diet δ 13 C (inferred from δ 13 C of preserved eggshells) spanning the last 140,000 years, using time‐series analysis. Using Akaike's information criterion, we compared two contrasting models: (1) there was an abrupt shift in δ 13 C coincident with the extinction of Genyornis , assumed 47.5 ka; and (2) there was a gradual shift in δ 13 C, correlated with reconstructed water level in Lake Eyre, a proxy for monsoon intensity. Results There was little evidence of an abrupt shift in emu diet δ 13 C about 45–50 ka, but δ 13 C appeared to steadily decrease between about 80 and 30 ka. Indeed, the model representing a correlation between δ 13 C and lake level was more than seven times more likely than the model representing an abrupt shift at 47.5 ka. Main conclusions The emu eggshell isotopic record from Lake Eyre does not support the hypothesis that landscape burning by humans transformed a savanna−grassland mosaic into the modern desert scrub, contributing to the extinction of Genyornis . While our findings cast strong doubt on the foremost line of evidence that landscape burning by humans caused the megafaunal extinctions, and suggest that central Australia was becoming increasingly arid in the Late Pleistocene, the relative roles of hunting by humans and climate change in the megafaunal extinctions remain unresolved.

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Environmental drivers, life strategies and bioindicator capacity of bryophyte communities in high-latitude headwater streams - P. Lang; K. J. Murphy (Hydrobiologia, 2012)

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

Distinguishing habitat types and the relative influences of environmental factors on patch occupancy for a butterfly metapopulation - Monte P. Sanford; Dennis D. Murphy; Peter F. Brussard (Journal of Insect Conservation, 2011)

Expansion of tubenose gobies Proterorhinus semilunaris into western Lake Erie and potential effects on native species - P. M. Kocovsky; J. A. Tallman; D. J. Jude; D. M. Murphy; J. E. Brown; C. A. Stepien (Biological Invasions, 2011)

Long-Term Trends in Chesapeake Bay Seasonal Hypoxia, Stratification, and Nutrient Loading - Rebecca R. Murphy; W. Michael Kemp; William P. Ball (Estuaries and Coasts, 2011)

Expression of Histone Deacetylases in Cellular Compartments of the Mouse Brain and the Effects of Ischemia - Selva Baltan; Amelia Bachleda; Richard S. Morrison; Sean P. Murphy (Translational Stroke Research, 2011)

Are the eucalypt and non-eucalypt components of Australian tropical savannas independent? - M. J. Lawes; B. P. Murphy; J. J. Midgley; J. Russell-Smith (Oecologia, 2011)

Characterisation and Deposition Studies of Recrystallised Lactose from Binary Mixtures of Ethanol/Butanol for Improved Drug Delivery from Dry Powder Inhalers - Waseem Kaialy; Gary P. Martin; Martyn D. Ticehurst; Paul Royall; Mohammad A. Mohammad; John Murphy; Ali Nokhodchi (The AAPS Journal, 2011)

Culturable Rhodobacter and Shewanella species are abundant in estuarine turbidity maxima of the Columbia River - S. L. Bräuer; C. Adams; K. Kranzler; D. Murphy; M. Xu; P. Zuber; H. M. Simon; A. M. Baptista; B. M. Tebo (Environmental Microbiology, 2011)
Summary Measurements of dissolved, ascorbate‐reducible and total Mn by ICP‐OES revealed significantly higher concentrations during estuarine turbidity maxima (ETM) events, compared with non‐events in the Columbia River. Most probable number (MPN) counts of Mn‐oxidizing or Mn‐reducing heterotrophs were not statistically different from that of other heterotrophs (10 3 –10 4 cells ml −1 ) when grown in defined media, but counts of Mn oxidizers were significantly lower in nutrient‐rich medium (13 cells ml −1 ). MPN counts of Mn oxidizers were also significantly lower on Mn(III)‐pyrophosphate and glycerol (21 cells ml −1 ). Large numbers of Rhodobacter spp. were cultured from dilutions of 10 −2 to 10 −5 , and many of these were capable of Mn(III) oxidation. Up to c . 30% of the colonies tested LBB positive, and all 77 of the successfully sequenced LBB positive colonies (of varying morphology) yielded sequences related to Rhodobacter spp. qPCR indicated that a cluster of Rhodobacter isolates and closely related strains (95–99% identity) represented approximately 1–3% of the total Bacteria , consistent with clone library results. Copy numbers of SSU rRNA genes for either Rhodobacter spp. or Bacteria were four to eightfold greater during ETM events compared with non‐events. Strains of a Shewanella sp. were retrieved from the highest dilutions (10 −5 ) of Mn reducers, and were also capable of Mn oxidation. The SSU rRNA gene sequences from these strains shared a high identity score (98%) with sequences obtained in clone libraries. Our results support previous findings that ETMs are zones with high microbial activity. Results indicated that Shewanella and Rhodobacter species were present in environmentally relevant concentrations, and further demonstrated that a large proportion of culturable bacteria, including Shewanella and Rhodobacter spp., were capable of Mn cycling in vitro .

Property Value Impacts of Hemlock Woolly Adelgid in Residential Forests - Thomas P. Holmes; Elizabeth A. Murphy; Kathleen P. Bell; Denise D. Royle (Forest Science, 2010)
This study estimates the economic losses attributable to a nonindigenous forest insect, the hemlock woolly adelgid (Adelges tsuga), using cross-sectional and difference-in-difference hedonic price models. The data span a decade of residential property value transactions in West Milford, New Jersey. Hemlock health in naturally regenerated hemlock stands was measured biannually over this period using remote sensing data and the image differencing technique. These data were linked with spatially referenced land use and land cover data, measured twice during the decade, and the locations and housing characteristics associated with parcels sold. Spatial dependence in the regression models was addressed using spatial error and fixed-effects panel data models. The empirical results demonstrated that hemlock decline consistently caused statistically significant reductions in property values both for parcels containing hemlock resources as well as for neighboring nonhemlock parcels. We conclude that failure to account for spatial spillover effects would downwardly bias estimates of economic losses and total economic losses on properties sold during the study period ranged from $0.64 million in the parcel level cross-section model to $2.2 million in the 0.5-km neighborhood difference-in-difference model.

Using generalized autoregressive error models to understand fire–vegetation–soil feedbacks in a mulga–spinifex landscape mosaic - Brett P. Murphy; Paolo Paron; Lynda D. Prior; Guy S. Boggs; Donald C. Franklin; David M. J. S. Bowman (Journal of Biogeography, 2010)
Aim To develop a new modelling approach for spatially autocorrelated non‐normal data, and apply it to a case study of the role that fire–vegetation–soil feedbacks play in maintaining boundaries between fire‐sensitive and fire‐promoted plant communities. Location A mulga ( Acacia aneura ) shrubland–spinifex ( Triodia spp.) grassland mosaic, central Australia. Methods Autoregressive error models were extended to non‐normal data by incorporating neighbourhood values of the response and predictor variables into generalized nonlinear models. These models were used to examine the environmental correlates of three response variables: mulga cover; fire frequency in areas free of mulga; and the presence of mulga banding. Mulga cover and mulga banding were assessed visually by overlaying 4477 × 1 km 2 grid cells on both Landsat 7 ETM+ and very high resolution imagery. Fire frequency was estimated from an existing fire history for central Australia, based on remotely sensed fire scars. Results The autoregressive error models explained 27%, 47% and 57% of the null deviance of mulga cover, fire frequency and mulga banding, respectively, with 12%, 15% and 24% of the null deviance being explained by environmental variables alone. These models accounted for virtually all residual spatial autocorrelation. While there was a clear negative relationship between mulga cover and fire frequency, there was little evidence that mulga was being restricted to parts of the landscape with inherently low fire frequencies. Mulga was most abundant at very low slope angles and on red earths, both of which are likely to reflect high site productivity, while fire frequency was not clearly affected by slope angle and was also relatively high on red earths. Main conclusions The modelling approach we have developed provides a much needed way of analysing spatially autocorrelated non‐normal data and can be easily incorporated into an information‐theoretic modelling framework. Using this approach, we provide evidence that mulga and spinifex have a highly antagonistic relationship. In more productive parts of the landscape, mulga suppresses spinifex and fire, while in less productive parts of the landscape, fire and spinifex suppress mulga, leading to the remarkable abruptness of mulga–spinifex boundaries that are maintained via fire–vegetation–soil feedbacks.

4-(4-Chloro-2-methylphenoxy)-N-hydroxybutanamide (CMH) targets mRNA of the c-FLIP variants and induces apoptosis in MCF-7 human breast cancer cells - Khadijeh Bijangi-Vishehsaraei; Mohammad Reza Saadatzadeh; Su Huang; Michael P. Murphy; Ahmad R. Safa (Molecular and Cellular Biochemistry, 2010)

Landscape genetics: where are we now? - ANDREW STORFER; MELANIE A. MURPHY; STEPHEN F. SPEAR; ROLF HOLDEREGGER; LISETTE P. WAITS (Molecular Ecology, 2010)
Landscape genetics has seen rapid growth in number of publications since the term was coined in 2003. An extensive literature search from 1998 to 2008 using keywords associated with landscape genetics yielded 655 articles encompassing a vast array of study organisms, study designs and methodology. These publications were screened to identify 174 studies that explicitly incorporated at least one landscape variable with genetic data. We systematically reviewed this set of papers to assess taxonomic and temporal trends in: (i) geographic regions studied; (ii) types of questions addressed; (iii) molecular markers used; (iv) statistical analyses used; and (v) types and nature of spatial data used. Overall, studies have occurred in geographic regions proximal to developed countries and more commonly in terrestrial vs. aquatic habitats. Questions most often focused on effects of barriers and/or landscape variables on gene flow. The most commonly used molecular markers were microsatellites and amplified fragment length polymorphism (AFLPs), with AFLPs used more frequently in plants than animals. Analysis methods were dominated by Mantel and assignment tests. We also assessed differences among journals to evaluate the uniformity of reporting and publication standards. Few studies presented an explicit study design or explicit descriptions of spatial extent. While some landscape variables such as topographic relief affected most species studied, effects were not universal, and some species appeared unaffected by the landscape. Effects of habitat fragmentation were mixed, with some species altering movement paths and others unaffected. Taken together, although some generalities emerged regarding effects of specific landscape variables, results varied, thereby reinforcing the need for species‐specific work. We conclude by: highlighting gaps in knowledge and methodology, providing guidelines to authors and reviewers of landscape genetics studies, and suggesting promising future directions of inquiry.

HUVEC ICAM-1 and VCAM-1 Synthesis in Response to Potentially Athero-Prone and Athero-Protective Mechanical and Nicotine Chemical Stimuli - Liam T. Breen; Peter E. McHugh; Bruce P. Murphy (Annals of Biomedical Engineering, 2010)

Using carbon isotope analysis of the diet of two introduced Australian megaherbivores to understand Pleistocene megafaunal extinctions - David M. J. S. Bowman; Brett P. Murphy; Clive R. McMahon (Journal of Biogeography, 2010)
Aim Australia lost a diverse assemblage of large marsupial herbivores in the late Pleistocene, with suggestions that the extinctions were biased towards browsers. In modern times two bovines, the Asian water buffalo ( Bubalus bubalis ) and banteng ( Bos javanicus ), have established feral populations in the Northern Territory, Australia. Buffalo have aggressively expanded throughout the savanna landscape, yet banteng remain near their point of introduction on the Cobourg Peninsula. We hypothesized that this difference is related to feeding ecology, possibly reflecting a legacy of the Pleistocene extinctions. Location Western Arnhem Land, Northern Territory, Australia. Methods Analysing a previously published dataset of body mass and feeding ecology of extinct and extant marsupial herbivores, we evaluated whether browsers were at greater risk of extinction than grazers. We compared the carbon isotope composition and nitrogen content of banteng and buffalo dung in order to evaluate the hypotheses that the differences in invasion success are related to feeding ecology, and that seasonal variation in browse consumption is linked to changing nutritional quality of grass. Results Controlling for body mass, the Pleistocene extinctions were clearly biased towards browsers. Introduced banteng appear to be primarily browsers, with their diets comprising 40% grass in the wet season and 15% in the late dry season. Buffalo have a more variable diet, with an increasing proportion of browse from the wet (30%) to the late dry season (75%), and can therefore be described as switching from grazer to browser. The decline of grass in the diet of both species appears to reflect the decline in the nutritional value of grass through the dry season, an inference supported by the negative relationship between δ 13 C values and the nitrogen content of dung. Main conclusions Banteng and buffalo are much larger than extant native herbivores, of which browsers are restricted to isolated rocky habitats. This suggests that banteng and buffalo have filled niches made vacant following the Pleistocene extinctions. The success of buffalo appears to be related to their greater dietary breadth, which enables them to graze and browse in eucalypt savannas, whilst the browsing banteng remain tethered to a mosaic of rain forest patches. The restriction of browsers may be a long‐range consequence of habitat transformations associated with Aboriginal landscape burning.

Coordinate loss of MHC class II expression in the diffuse large B cell lymphoma cell line OCI-Ly2 is due to a novel mutation in RFX-AP - Meghan Bushway; Kelly A. Cycon; Kathleen Mulvaney; Shawn P. Murphy (Immunogenetics, 2010)

Frequent fires reduce tree growth in northern Australian savannas: implications for tree demography and carbon sequestration - BRETT P. MURPHY; JEREMY RUSSELL‐SMITH; LYNDA D. PRIOR (Global Change Biology, 2010)
Tropical savannas are typically highly productive yet fire‐prone ecosystems, and it has been suggested that reducing fire frequency in savannas could substantially increase the size of the global carbon sink. However, the long‐term demographic consequences of modifying fire regimes in savannas are difficult to predict, with the effects of fire on many parameters, such as tree growth rates, poorly understood. Over 10 years, we examined the effects of fire frequency on the growth rates (annual increment of diameter at breast height) of 3075 tagged trees, at 137 locations throughout the mesic savannas of Kakadu, Nitmiluk and Litchfield National Parks, in northern Australia. Frequent fires substantially reduced tree growth rates, with the magnitude of the effect markedly increasing with fire severity. The highest observed frequencies of mild, moderate and severe fires (1.0, 0.8 and 0.4 fires yr −1 , respectively) reduced tree growth by 24%, 40% and 66% respectively, relative to unburnt areas. These reductions in tree growth imply reductions in the net primary productivity of trees by between 0.19 t C ha −1 yr −1 , in the case of mild fires, and 0.51 t C ha −1 yr −1 , in the case of severe fires. Such reductions are relatively large, given that net biome productivity (carbon sequestration potential) of these savannas is estimated to be just 1–2 t C ha −1 yr −1 . Our results suggest that current models of savanna tree demography, that do not account for a relationship between severe fire frequency and tree growth rate, are likely to underestimate the long‐term negative effects of frequent severe fires on tree populations. Additionally, the negative impact of frequent severe fires on carbon sequestration rates may have been underestimated; reducing fire frequencies in savannas may increase carbon sequestration to a greater extent than previously thought.

Environmental predictors of the occurrence of exotic Hydrilla verticillata (L.f.) Royle and native Egeria najas Planch. in a sub-tropical river floodplain: the Upper River Paraná, Brazil - W. T. Z. Sousa; S. M. Thomaz; K. J. Murphy; M. J. Silveira; R. P. Mormul (Hydrobiologia, 2009)

Testosterone: from initiating change to modulating social organisation in domestic fowl (Gallus gallus domesticus) - John P. Kent; Kenneth J. Murphy; Finian J. Bannon; Niamh M. Hynes; Thomas J. Hayden (The Science of Nature, 2009)

The endothelial microparticle response to a high fat meal is not attenuated by prior exercise - Michael Harrison; Ronan P. Murphy; Paul L. O’Connor; Donal J. O’Gorman; Noel McCaffrey; Philip M. Cummins; Niall M. Moyna (European Journal of Applied Physiology, 2009)

Circulating fatty acids and prostate cancer risk in a nested case–control study: the Multiethnic Cohort - Song-Yi Park; Lynne R. Wilkens; Susanne M. Henning; Loïc Le Marchand; Kun Gao; Marc T. Goodman; Suzanne P. Murphy; Brian E. Henderson; Laurence N. Kolonel (Cancer Causes & Control, 2009)

Effects of Urban Development on Ant Communities: Implications for Ecosystem Services and Management - MONTE P. SANFORD; PATRICIA N. MANLEY; DENNIS D. MURPHY (Conservation Biology, 2009)
Research that connects the effects of urbanization on biodiversity and ecosystem services is lacking. Ants perform multifarious ecological functions that stabilize ecosystems and contribute to a number of ecosystem services. We studied responses of ant communities to urbanization in the Lake Tahoe basin by sampling sites along a gradient of urban land development. We sampled ant communities, measured vegetation characteristics, quantified human activities, and evaluated ant‐community responses by grouping ants into service‐providing units (SPUs), defined as a group of organisms and their populations that perform specific ecosystem services, to provide an understanding of urbanization impacts on biodiversity and their delivery of ecosystem services. Species richness and abundance peaked at intermediate levels of urban development, as did the richness of 3 types of ant SPUs (aerators, decomposers, and compilers). With increasing land development aerator and decomposer ants significantly declined in abundance, whereas compiler ants significantly increased in abundance. Competing models demonstrated that precipitation was frequently among the strongest influences on ant community structure; however, urban development and human activities also had a strong, negative influence on ants, appearing in most models with ΔAIC c

Independent colonization and extensive cryptic speciation of freshwater amphipods in the isolated groundwater springs of Australia's Great Artesian Basin - NICHOLAS P. MURPHY; MARK ADAMS; ANDREW D. AUSTIN (Molecular Ecology, 2009)
The groundwater‐dependent springs of the Great Artesian Basin (GAB) in arid inland Australia represent a unique and threatened ecosystem. These incredibly isolated springs support a diverse array of endemic flora and fauna. One of the common faunal groups in the GAB springs is the freshwater amphipods of the family Chiltoniidae. The morphological conservatism and taxonomic uncertainty associated with these amphipods has ensured their true biodiversity, phylogeographical history and evolutionary affinities have remained unknown. We have used mitochondrial DNA and allozyme data to unravel a complicated history of isolation, extinction and dispersal among spring amphipod populations across the GAB. The results provide evidence for multiple independent colonizations in the GAB springs, particularly within the Lake Eyre group of springs. The inclusion of a group of Western Australian (WA) stygobitic amphipods from populations up to 1500 km away found surprising evidence for a shared evolutionary history between stygobitic and GAB spring amphipods. Approximate dating of the diversity found between major clades suggests the majority of lineages originated in the late Miocene, around the time of the aridification of inland Australia. The large number of independent lineages and the close connection between GAB spring and WA stygobitic amphipods suggest that a significantly rich amphipod fauna existed in the much wetter environment that once existed in inland Australia. The results also provide evidence for a gross underestimation of the species diversity within the springs, with 12 putative species identified, a conclusion with significant implications for the ongoing conservation of the GAB springs.

Direct effects of diazepam on emotional processing in healthy volunteers - S. E. Murphy; C. Downham; P. J. Cowen; C. J. Harmer (Psychopharmacology, 2008)

Bioengineering and Imaging Research Opportunities Workshop V: A Summary - William R. Hendee; Kevin Cleary; Richard L. Ehman; Gary D. Fullerton; Warren S. Grundfest; John Haller; Christine Kelley; Anne E. Meyer; Robert F. Murphy; William Phillips; Vladimir P. Torchilin (Annals of Biomedical Engineering, 2008)

Modulation of steroidogenesis by coastal waters and sewage effluents of Hong Kong, China, using the H295R assay - Tannia Gracia; Paul D. Jones; Eric B. Higley; Klara Hilscherova; John L. Newsted; Margaret B. Murphy; Alice K. Y. Chan; Xiaowei Zhang; Markus Hecker; Paul K. S. Lam; Rudolf S. S. Wu; John P. Giesy (Environmental Science and Pollution Research, 2008)

A Rapid Simultaneous Saccharification and Fermentation (SSF) Technique to Determine Ethanol Yields - Asli Isci; Patrick T. Murphy; Robert P. Anex; Kenneth J. Moore (BioEnergy Research, 2008)

Neurochemical responses to antidepressants in the prefrontal cortex of mice and their efficacy in preclinical models of anxiety-like and depression-like behavior: a comparative and correlational study - Tomohiro Kobayashi; Etsuko Hayashi; Midori Shimamura; Mine Kinoshita; Niall P. Murphy (Psychopharmacology, 2008)

Evidence for a transposition event in a second NITR gene cluster in zebrafish - Jeffrey A. Yoder; John P. Cannon; Ronda T. Litman; Carly Murphy; Jennifer L. Freeman; Gary W. Litman (Immunogenetics, 2008)

Microbial response to the addition of glucose in low-fertility soils - F. C. Hoyle; D. V. Murphy; P. C. Brookes (Biology and Fertility of Soils, 2008)

Pm37, a new broadly effective powdery mildew resistance gene from Triticum timopheevii - L. D. Perugini; J. P. Murphy; D. Marshall; G. Brown-Guedira (Theoretical and Applied Genetics, 2008)

Foraging by Two Estuarine Fishes, Fundulus heteroclitus and Fundulus majalis, on Juvenile Asian Shore Crabs (Hemigrapsus sanguineus) in Western Long Island Sound - Diane J. Brousseau; Anna E. Murphy; Nicole P. Enriquez; Kara Gibbons (Estuaries and Coasts, 2008)

Global diversity of aquatic macrophytes in freshwater - P. A. Chambers; P. Lacoul; K. J. Murphy; S. M. Thomaz (Hydrobiologia, 2008)

Role of lipase in Burkholderia cepacia complex (Bcc) invasion of lung epithelial cells - T. Mullen; K. Markey; P. Murphy; S. McClean; M. Callaghan (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Dietary fiber and colorectal cancer risk: the multiethnic cohort study - Abraham M. Y. Nomura; Jean H. Hankin; Brian E. Henderson; Lynne R. Wilkens; Suzanne P. Murphy; Malcolm C. Pike; Loic Le Marchand; Daniel O. Stram; Kristine R. Monroe; Laurence N. Kolonel (Cancer Causes & Control, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The impact of time and field conditions on brown bear (Ursus arctos) faecal DNA amplification - Melanie A. Murphy; Katherine C. Kendall; Andrew Robinson; Lisette P. Waits (Conservation Genetics, 2007)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Chromosomal location of Pm35, a novel Aegilops tauschii derived powdery mildew resistance gene introgressed into common wheat (Triticum aestivum L.) - L. M. Miranda; J. P. Murphy; D. Marshall; C. Cowger; S. Leath (Theoretical and Applied Genetics, 2007)

Comparison of antibiotic susceptibility of Burkholderia cepacia complex organisms when grown planktonically or as biofilm in vitro - E. Caraher; G. Reynolds; P. Murphy; S. McClean; M. Callaghan (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Body mass index and physical activity as risk factors for pancreatic cancer: the Multiethnic Cohort Study - Ute Nöthlings; Lynne R. Wilkens; Suzanne P. Murphy; Jean H. Hankin; Brian E. Henderson; Laurence N. Kolonel (Cancer Causes & Control, 2007)

Seasonal water availability predicts the relative abundance of C 3 and C 4 grasses in Australia - Brett P. Murphy; David M. J. S. Bowman (Global Ecology and Biogeography, 2007)
Aim Numerous studies have examined the climatic factors that influence the abundance of C 4 species within the grass flora (C 4 relative species richness) in various regions throughout the world, but very few have examined the relative abundance of C 4 vs. C 3 grasses (C 4 relative abundance). We sought to determine the climatic factors that influence C 4 relative abundance throughout Australia. Location Australia (including Tasmania). Methods We measured C 4 relative abundance at 168 locations and measured δ 13 C (the abundance of 13 C relative to 12 C) of the bone collagen of 779 kangaroos collected throughout Australia, as bone collagen δ 13 C was assumed to be proportional to the relative abundance of C 4 grasses in the diet. Results Both C 4 relative abundance and kangaroo bone collagen δ 13 C were found to have a strong positive relationship with seasonal water availability, i.e. the distribution of rainfall in the C 4 vs. C 3 growing seasons (76% and 69% of deviance explained, respectively). There was clear evidence that seasonal water availability was a better predictor of both C 4 relative abundance and bone collagen δ 13 C than other climate variables such as mean annual temperature and January daily minimum temperature. However, seasonal water availability appeared to be a relatively poor predictor of C 4 relative species richness, which was most closely related to January daily minimum temperature (90% of deviance explained). Main conclusions Our results highlight the relatively poor relationship between C 4 relative abundance and C 4 relative species richness, and suggest that these two variables may be related to different climatic factors. They also suggest that caution is required when using C 4 relative species richness to infer the relative biomass and productivity of C 4 grasses on a global scale.

The interdependence of fire, grass, kangaroos and Australian Aborigines: a case study from central Arnhem Land, northern Australia - Brett P. Murphy; David M. J. S. Bowman (Journal of Biogeography, 2007)
Aim To describe the nexus between Aboriginal landscape burning and patterns of habitat use by kangaroos in a tropical savanna habitat mosaic, and to provide evidence to evaluate the claim that Aboriginal landscape burning is a game management tool. Location Central Arnhem Land, a stronghold of traditional Aboriginal culture, in the monsoon tropics of northern Australia. Methods The abundance of kangaroo scats was recorded throughout a landscape burnt by Aboriginal people, and used as a proxy for the intensity of habitat use by kangaroos. Scat abundance was assessed along field traverses totalling 112 km, at three time periods: (1) 1–4 weeks following mid‐dry season burning (July 2003); (2) in the late dry season (November 2003); and (3) in the following mid‐dry season (July 2004). We compared the intensity with which kangaroos used burnt vs. unburnt areas in various habitat types, with time since mid‐dry season burning. Scats were collected from areas that had been burnt to a varying extent and the abundance of carbon and nitrogen stable isotopes ( δ 13 C and δ 15 N) and carbon to nitrogen ratios (C : N) determined. Results There was clear evidence of an interaction between burning and habitat type on the abundance of kangaroo scats. Scats were much more abundant in burnt vs. unburnt areas in the moist habitats, but the opposite effect was observed in the dry rocky habitats, with higher scat abundance in unburnt areas. This interactive effect of burning and habitat type on scat abundance was observed immediately ( Main conclusions The fine‐scale mosaic of burnt and unburnt areas created by mid‐dry season Aboriginal landscape burning has clear effects on the distribution of kangaroos. Kangaroos move into burnt moist habitats and away from burnt dry, rocky habitats. Isotopic analysis of scats suggests that the mechanism driving this effect is the increased abundance of nitrogen rich grasses in burnt moist habitats.

Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Angela M. Murphy; David E. MacHugh; Stephen D.E. Park; Erik Scraggs; Chris S. Haley; David J. Lynn; Maurice P. Boland; Michael L. Doherty (Mammalian Genome, 2007)

Pm34: a new powdery mildew resistance gene transferred from Aegilops tauschii Coss. to common wheat (Triticum aestivum L.) - L. M. Miranda; J. P. Murphy; D. Marshall; S. Leath (Theoretical and Applied Genetics, 2006)

Preface: Organising knowledge on aquatic plants: the European Weed Research Society and scientific networks - J. M. Caffrey; A. Dutartre; J. Haury; K. J. Murphy; P. M. Wade (Hydrobiologia, 2006)

Predicting interactions between wetland vegetation and the soil-water and surface-water environment using diversity, abundance and attribute values - M. P. Kennedy; K. J. Murphy; D. J. Gilvear (Hydrobiologia, 2006)

Sediment TCDD-EQs and EROD and MROD Activities in Ranid Frogs from Agricultural and Nonagricultural Sites in Michigan (USA) - M. B. Murphy; M. Hecker; K. K. Coady; A. R. Tompsett; P. D. Jones; J. L. Newsted; H. L. Wong; L. H. du Preez; K. R. Solomon; J. A. Carr; E. E. Smith; R. J. Kendall; et al. (Archives of Environmental Contamination and Toxicology, 2006)

Gene expression analysis in a canine model of X-linked Alport syndrome - Kimberly A. Greer; Marnie A. Higgins; Melissa L. Cox; Timothy P. Ryan; Brian R. Berridge; Clifford E. Kashtan; George E. Lees; Keith E. Murphy (Mammalian Genome, 2006)

Evidence of an oscillating peripheral clock in an equine fibroblast cell line and adipose tissue but not in peripheral blood - Barbara A. Murphy; Mandi M. Vick; Dawn R. Sessions; R. Frank Cook; Barry P. Fitzgerald (Journal of Comparative Physiology A, 2006)

Distribution of orogenic gold deposits in relation to fault zones and gravity gradients: targeting tools applied to the Eastern Goldfields, Yilgarn Craton, Western Australia - Frank P. Bierlein; Finbarr C. Murphy; Roberto F. Weinberg; Terry Lees (Mineralium Deposita, 2006)

Contrasting population changes in sympatric penguin species in association with climate warming - JAUME FORCADA; P. N. TRATHAN; K. REID; E. J. MURPHY; J. P. CROXALL (Global Change Biology, 2006)
Climate warming and associated sea ice reductions in Antarctica have modified habitat conditions for some species. These include the congeneric Adélie, chinstrap and gentoo penguins, which now demonstrate remarkable population responses to regional warming. However, inconsistencies in the direction of population changes between species at different study sites complicate the understanding of causal processes. Here, we show that at the South Orkney Islands where the three species breed sympatrically, the less ice‐adapted gentoo penguins increased significantly in numbers over the last 26 years, whereas chinstrap and Adélie penguins both declined. These trends occurred in parallel with regional long‐term warming and significant reduction in sea ice extent. Periodical warm events, with teleconnections to the tropical Pacific, caused cycles in sea ice leading to reduced prey biomass, and simultaneous interannual population decreases in the three penguin species. With the loss of sea ice, Adélie penguins were less buffered against the environment, their numbers fluctuated greatly and their population response was strong and linear. Chinstrap penguins, considered to be better adapted to ice‐free conditions, were affected by discrete events of locally increased ice cover, but showed less variable, nonlinear responses to sea ice loss. Gentoo penguins were temporarily affected by negative anomalies in regional sea ice, but persistent sea ice reductions were likely to increase their available niche, which is likely to be substantially segregated from that of their more abundant congeners. Thus, the regional consequences of global climate perturbations on the sea ice phenology affect the marine ecosystem, with repercussions for penguin food supply and competition for resources. Ultimately, variability in penguin populations with warming reflects the local balance between penguin adaptation to ice conditions and trophic‐mediated changes cascading from global climate forcing.

An AFLP-based survey of genetic diversity among accessions of sea oats (Uniola paniculata, Poaceae) from the southeastern Atlantic and Gulf coast states of the United States - Prasanta K. Subudhi; Neil P. Parami; Stephen A. Harrison; Michael D. Materne; J. Paul Murphy; David Nash (Theoretical and Applied Genetics, 2005)

Complete Mitochondrial DNA Sequences of the Decapod Crustaceans Pseudocarcinus gigas (Menippidae) and Macrobrachium rosenbergii (Palaemonidae) - Adam D. Miller; Nicholas P. Murphy; Christopher P. Burridge; Christopher M. Austin (Marine Biotechnology, 2005)

Microsatellite analysis indicates an absence of population structure among Hippoglossus hippoglossus in the north‐west Atlantic - D. P. Reid; S. Pongsomboon; T. Jackson; C. McGowan; C. Murphy; D. Martin‐Robichaud; M. Reith (Journal of Fish Biology, 2005)
To explore the population structure of Atlantic halibut Hippoglossus hippoglossus , 160 fish from four locations in the north‐west Atlantic (Bay of Fundy, Scotian Shelf, Gulf of St Lawrence and Iceland) were examined for evidence of population structure using 18 microsatellite markers. Pair‐wise F ST and a model‐based cluster analysis revealed no significant differentiation between samples, although uncertainties surrounding Atlantic halibut reproductive behaviour made it difficult to ascertain that only a single breeding population had been sampled at each location

Using Indicator Species to Predict Species Richness of Multiple Taxonomic Groups - ERICA FLEISHMAN; JAMES R. THOMSON; RALPH MAC NALLY; DENNIS D. MURPHY; JOHN P. FAY (Conservation Biology, 2005)
Values of species richness are used widely to establish conservation and management priorities. Because inventory data, money, and time are limited, use of surrogates such as “indicator” species to estimate species richness has become common. Identifying sets of indicator species that might reliably predict species richness, especially across taxonomic groups, remains a considerable challenge. We used genetic algorithms and a Bayesian approach to explain individual and combined species richness of two taxonomic groups as a function of occurrence patterns of indicator species drawn from either both groups or one group. Genetic algorithms iteratively screen large numbers of potential models and predictor variables in a process that emulates natural selection. The best‐fitting models of bird species richness and butterfly species richness explained approximately 80% of deviances and included only indicator species from the same taxonomic group. Using species from both taxonomic groups as potential predictors did not improve model fit but slightly improved the parsimony (fewer predictors) of the model of bird species richness. The best model of combined species richness included five butterflies and one bird and explained 83% of deviance, whereas a model of combined species richness based on six butterflies as indicators explained 82% of deviance. A model of combined species richness based on birds alone explained 72% of deviance. We found that a small, common set of species could be used to predict separately the species richness of multiple taxonomic groups. We built models explaining approximately 70% of the deviance in species richness of birds and butterflies based on a common set of three bird species and three butterfly species. We also identified a set of six species of butterflies that predicted ≥66% of both bird species richness and butterfly species richness. Our approach is applicable to any assemblage or ecosystem, and may be useful both for estimating species richness and for gaining insight into mechanisms that influence diversity patterns.

Impact of the European Antimicrobial Resistance Surveillance System on the development of a national programme to monitor resistance in Staphylococcus aureus and Streptococcus pneumoniae in Ireland, 1999–2003 - O. M. Murphy; S. Murchan; D. Whyte; H. Humphreys; A. Rossney; P. Clarke; R. Cunney; C. Keane; L. E. Fenelon; D. O’Flanagan (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Environmental Consequences of Intensively Managed Forest Plantations in the Pacific Northwest - John P. Hayes; Stephen H. Schoenholtz; Mitschka J. Hartley; Glen Murphy; Robert F. Powers; Dean Berg; Steven R. Radosevich (Journal of Forestry, 2005)
Environmental consequences of intensively managed forest plantations (IMFP) are manifested primarily through influences on biodiversity, soils, and water resources. These consequences may be positive, neutral, or negative, depending on the spatial and temporal context and site-specificdetails. Many aspects of environmental consequences of IMFPs are increasingly understood, but significant gaps in our knowledge remain. Societal environmental goals and objectives of IMFPs remain poorly articulated and fuel a lively, often heated, social dialogue that will likely continuefor some time to come.

Phylogenetic relationships of the globally distributed freshwater prawn genus Macrobrachium (Crustacea: Decapoda: Palaemonidae): biogeography, taxonomy and the convergent evolution of abbreviated larval development - Nicholas P. Murphy; Christopher M. Austin (Zoologica Scripta, 2005)
There has hitherto been little research into evolutionary and taxonomic relationships amongst species of the freshwater prawn genus Macrobrachium Bate across its global distribution. Previous work by the authors demonstrated that the endemic Australian species did not evolve from a single ancestral lineage. To examine whether other regional Macrobrachium faunas also reflect this pattern of multiple origins, the phylogeny of 30 Macrobrachium species from Asia, Central/South America and Australia was inferred from mitochondrial 16S rRNA sequences. Phylogenetic relationships demonstrate that, despite some evidence for regional diversification, Australia, Asia and South America clearly contain Macrobrachium species that do not share a common ancestry, suggesting that large‐scale dispersal has been a major feature of the evolutionary history of the genus. The evolution of abbreviated larval development (ALD), associated with the transition from an estuarine into a purely freshwater lifecycle, was also mapped onto the phylogeny and was shown to be a relatively homoplasious trait and not taxonomically informative. Other taxonomic issues, as well as the evolutionary origins of Macrobrachium , are also discussed.

Comparing the effects of farming practices on ground beetle (Coleoptera: Carabidae) and spider (Araneae) assemblages of Scottish farmland - Lorna J. Cole; David I. McCracken; Iain S. Downie; Peter Dennis; Garth N. Foster; Tony Waterhouse; Kevin J. Murphy; Anna L. Griffin; Mike P. Kennedy (Biodiversity and Conservation, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Twinning and the Incidence of Breast and Gynecological Cancers (United States) - Rachel E. Neale; David M. Purdie; Michael F. G. Murphy; Geraldine P. Mineau; Timothy Bishop; David C. Whiteman (Cancer Causes & Control, 2004)

Phylogeography of the widespread Australian freshwater prawn, Macrobrachium australiense (Decapoda, Palaemonidae) - Nicholas P. Murphy; Christopher M. Austin (Journal of Biogeography, 2004)
Aim To investigate the phylogeographic structure of the widespread freshwater prawn, Macrobrachium australiense , within and between major Australian drainage basins using mitochondrial sequence data. This will enable the investigation of historical connections between major drainages and examination of hypotheses of biogeographic associations among Australian freshwater basins. Location Inland, eastern and northern Australia. Methods Sequencing 16S rRNA and ATPase 6 protein coding mitochondrial DNA genes from M. australiense from 19 locations from inland, eastern and northern Australia. Results Within drainage basins, haplotype trees are monophyletic, with the exception of the Finke River from the Lake Eyre Basin. Macrobrachium australiense from the two main inland drainages, the Murray–Darling and Lake Eyre Basin are divergent from each other and do not form a monophyletic group, instead the Murray–Darling Basin haplotypes clade with eastern coastal haplotypes. Haplotypes from neighbouring eastern coastal drainages were found to be quite divergent from each other. Main conclusions The phylogeographic relationships among M. australiense suggest that the two major inland drainages, the Murray–Darling Basin and the Lake Eyre Basin, are not biogeographically closely associated to each other. Instead the Murray–Darling Basin is more closely allied with the eastern coastal drainages across the Great Dividing Range. Despite their proximity the neighbouring southeast Queensland coastal Mary and Brisbane Rivers are also biogeographically divergent from each other. The results also indicate that the Finke River appears to have been isolated from the remainder of the Lake Eyre Basin catchment for a significant period of time.

Central administration of nociceptin/orphanin FQ blocks the acquisition of conditioned place preference to morphine and cocaine, but not conditioned place aversion to naloxone in mice - Kazuto Sakoori; Niall P. Murphy (Psychopharmacology, 2004)

Coronary Stent Strut Size Dependent Stress–Strain Response Investigated Using Micromechanical Finite Element Models - P. Savage; B. P. O' Donnell; P. E. McHugh; B. P. Murphy; D. F. Quinn (Annals of Biomedical Engineering, 2004)

Experimental growth responses to groundwater level variation and competition in five British wetland plant species - Michael P. Kennedy; Judith M. Milne; Kevin J. Murphy (Wetlands Ecology and Management, 2003)

Oceanographic variability and changes in Antarctic krill ( Euphausia superba ) abundance at South Georgia - P. N. Trathan; A. S. Brierley; M. A. Brandon; D. G. Bone; C. Goss; S. A. Grant; E. J. Murphy; J. L. Watkins (Fisheries Oceanography, 2003)
Oceanographic data collected to the north of South Georgia were examined for three consecutive summers (1996/97, 1997/98, 1998/99). The results show the existence of a shelf break front during each period. The most reliable means of defining the front was the potential density anomaly at the near‐surface potential temperature minimum. In each year, off‐shelf waters were separated from on‐shelf waters by water with a potential density anomaly between 27.22 and 27.29 kg m −3 . During 1997/98, the near‐surface potential temperature minimum was much colder and much shallower than in other years and was consistent with waters originating from much further south than South Georgia; these differences were further evident at a single deep off‐shelf station. The oceanographic changes during 1997/98 were consistent with a mesoscale or large‐scale movement of the southern Antarctic Circumpolar Current front. Acoustically determined densities of Antarctic krill, Euphausia superba , at South Georgia showed consistent patterns between years. Densities were substantially higher over the shelf compared with off‐shelf, with the highest densities at the shelf edge; densities were also higher to the east of the island. During 1997/98, acoustic densities of krill were substantially higher than in other years. The coincidence of the elevated acoustic density and the cooler oceanographic conditions was explored. When data from all years were combined and analysed by Generalized Additive Model, an inverse relationship between acoustic density and temperature was apparent. Historical data were also examined and it was noted that the only other occurrence of such a high estimate of krill density at South Georgia, was when oceanographic conditions were also colder.

Genetic Variation Within Chinese and Western Cultivated Oat Accessions - G. Baohong; X. Zhou; J. P. Murphy (Cereal Research Communications, 2003)

The influence of diet on faecal DNA amplification and sex identification in brown bears ( Ursus arctos ) - Melanie A. Murphy; Lisette P. Waits; Katherine C. Kendall (Molecular Ecology, 2003)
To evaluate the influence of diet on faecal DNA amplification, 11 captive brown bears ( Ursus arctos ) were placed on six restricted diets: grass ( Trifolium spp., Haplopappus hirtus and Poa pratensis ), alfalfa ( Lupinus spp.), carrots ( Daucus spp.), white‐tailed deer ( Odocoileus virginianus ), blueberries ( Vaccinium spp.) and salmon ( Salmo spp.). DNA was extracted from 50 faecal samples of each restricted diet, and amplification of brown bear DNA was attempted for a mitochondrial DNA (mtDNA) locus and nuclear DNA (nDNA) locus. For mtDNA, no significant differences were observed in amplification success rates across diets. For nDNA, amplification success rates for salmon diet extracts were significantly lower than all other diet extracts ( P

The Stress–Strain Behavior of Coronary Stent Struts is Size Dependent - B. P. Murphy; P. Savage; P. E. McHugh; D. F. Quinn (Annals of Biomedical Engineering, 2003)

Sequence Analysis of the Washington/1964 strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild Type Recombinant HPIV1 Produced by Reverse Genetics - J. T. Newman; S. R. Surman; J. M. Riggs; Chris T. Hansen; P. L. Collins; B. R. Murphy; M.H. Skiadopoulos (Virus Genes, 2003)

Pythium spp. from cavity spot and other root diseases of Australian carrots - E. M. Davison; G. C. MacNish; P. A. Murphy; A. G. McKay (Australasian Plant Pathology, 2003)

An evaluation of long-term preservation methods for brown bear (Ursus arctos) faecal DNA samples - Melanie A. Murphy; Lisette P. Waits; Katherine C. Kendall; Samuel K. Wasser; Jerry A. Higbee; Robert Bogden (Conservation Genetics, 2002)

The effects of tryptophan depletion on cognitive and affective processing in healthy volunteers - F. Murphy; K. Smith; P. Cowen; T. Robbins; B. Sahakian (Psychopharmacology, 2002)

Development of Multiplexed Fluorescence Microbead Covalent Assays (FMCAs) for Pesticide Biomonitoring - R. E. Biagini; D. M. Murphy; D. L. Sammons; J. P. Smith; C. A. F. Striley; B. A. MacKenzie (Bulletin of Environmental Contamination and Toxicology, 2002)

Genus Coltivirus (family Reoviridae): genomic and morphologic characterization of Old World and New World viruses - H. Attoui; F. Mohd Jaafar; P. Biagini; J.-F. Cantaloube; P. de Micco; F. A. Murphy; X. de Lamballerie (Archives of Virology, 2002)

Modeling and Predicting Species Occurrence Using Broad‐Scale Environmental Variables: an Example with Butterflies of the Great Basin - Erica Fleishman; Ralph Mac Nally; John P. Fay; Dennis D. Murphy (Conservation Biology, 2001)
If occurrence of individual species can be modeled as a function of easily quantified environmental variables (e.g., derived from a geographic information system [GIS]) and the predictions of these models are demonstrably successful, then the scientific foundation for management planning will be strengthened. We used Bayesian logistic regression to develop predictive models for resident butterflies in the central Great Basin of western North America. Species inventory data and values for 14 environmental variables from 49 locations (segments of canyons) in the Toquima Range ( Nevada, U.S.A.) were used to build the models. Squares of the environmental variables were also used to accommodate possibly nonmonotonic responses. We obtained statistically significant models for 36 of 56 (64%) resident species of butterflies. The models explained 8–72% of the deviance in occurrence of those species. Each of the independent variables was significant in at least one model, and squared versions of five variables contributed to models. Elevation was included in more than half of the models. Models included one to four variables; only one variable was significant in about half the models. We conducted preliminary tests of two of our models by using an existing set of data on the occurrence of butterflies in the neighboring Toiyabe Range. We compared conventional logistic classification with posterior probability distributions derived from Bayesian modeling. For the latter, we restricted our predictions to locations with a high ( 70%) probability of predicted presence or absence. We will perform further tests after conducting inventories at new locations in the Toquima Range and nearby Shoshone Mountains, for which we have computed environmental variables by using remotely acquired topographic data, digital‐terrain and microclimatic models, and GIS computation.

Prediction of uphill time-trial bicycling performance in humans with a scaling-derived protocol - D. P. Heil; O. F. Murphy; A. R. Mattingly; B. K. Higginson (European Journal of Applied Physiology, 2001)

Phytoplankton distributions around New Zealand derived from SeaWiFS remotely‐sensed ocean colour data - R. J. Murphy; M. H. Pinkerton; K. M. Richardson; J. M. Bradford‐Grieve; P. W. Boyd (New Zealand Journal of Marine and Freshwater Research, 2001)
Ocean colour data from the NASA Sea‐viewing Wide Field‐of‐view Sensor (SeaWiFS) was used to estimate chlorophyll a concentration around New Zealand on a monthly basis between September 1997 and May 2000. The performance of the SeaWiFS chlorophyll a algorithm (OC4v4) was investigated by comparing in situ measurements of the underwater light field with measurements of phytoplankton pigment concentration by High Performance Liquid Chromatography. The algorithm performed well for chlorophyll a concentrations below 0.6 mg m‐3 but overestimated by a factor of two or more at higher concentrations. The average chlorophyll a concentration for New Zealand Exclusive Economic Zone was calculated as an indication of the overall productivity of the region and varied between 0.26 and 0.43 mg m‐3 with no obvious relationship to the Southern Oscillation Index. New Zealand northern subtropical and Tasman Sea waters had a classical cycle of spring and autumn chlorophyll blooms consistent with production being co‐limited by nitrate and light. Subantarctic waters had a low‐magnitude annual cycle of chlorophyll abundance that peaked in early autumn, consistent with production being predominantly limited by a combination of iron and light. Chlorophyll was generally highest in the Subtropical Front where subtropical and subantarctic waters mix. A series of persistent warm‐core eddies along New Zealand's east coast was obvious in many images, manifest as regions of low chlorophyll concentration.

Effects of temperature, and availability of nitrogen and phosphorus on the abundance of Anabaena and Microcystis in Lake Biwa, Japan: an experimental approach - C. Nalewajko; T. P. Murphy (Limnology, 2001)

Effective Planning and Implementation of Ecological Rehabilitation Projects: A Case Study of the Regional Municipality of Waterloo (Ontario, Canada) - LARRY R. G. MARTIN; STEPHEN D. MURPHY; SOONYA P. Quon (Environmental Management, 2001)

Sexual size dimorphism in fallow deer (Dama dama): do larger, heavier males gain greater mating success? - Alan G. McElligott; Martin P. Gammell; Hilda C. Harty; Dean R. Paini; Desmond T. Murphy; James T. Walsh; Thomas J. Hayden (Behavioral Ecology and Sociobiology, 2001)

Signal Transduction in Resistance to Plant Viruses - Alex M. Murphy; Androulla Gilliland; Chui Eng Wong; Joanne West; Davinder P. Singh; John P. Carr (European Journal of Plant Pathology, 2001)

Bi-directional changes in synaptic plasticity induced at corticostriatal synapses in vitro - Jonathan P. Spencer; Kerry P.S.J. Murphy (Experimental Brain Research, 2000)

Upsides and downsides: contrasting topographic gradients in species richness and associated scenarios for climate change - Erica Fleishman; John P. Fay; Dennis D. Murphy (Journal of Biogeography, 2000)
Aim We tested whether montane butterflies exhibit similar responses to elevation in two adjacent mountain ranges in the Great Basin; whether surface water availability, canyon depth and canyon width vary predictably with elevation; and whether those factors act in conjunction with elevation to generate the observed gradients in species richness. These variables might reasonably be expected to affect species richness of butterflies and can be derived readily for most landscapes. We also explored how climate change may affect species distributions in both mountain ranges. Location Field research was conducted in the Toiyabe and Toquima ranges, Lander and Nye counties, Nevada, USA. Methods We obtained data for 102 locations in the Toiyabe Range and 49 locations in the Toquima Range. These locations covered an elevational gradient of c. 1350 m in the Toiyabe Range and 900 m in the Toquima Range. Species richness data were based upon comprehensive field inventories. Elevation was measured by differentially corrected global positioning systems. Values for the remaining predictive variables were derived using geographic information systems. Availability of surface water was quantified as the distance from the centre of the inventory route to the nearest permanent source of running or standing water. Results In the Toiyabe Range, species richness decreases as elevation increases. Water availability and canyon depth and width vary predictably with elevation, but do not interact with elevation to affect species richness patterns. In the Toquima range, in contrast, species richness increases as elevation increases, and no other predictive variable covaries with elevation. Main conclusions We suggest that range‐specific gradients in climatic severity contribute to the distinct elevational gradients in species richness. In the face of climate change, species richness patterns in the Toquima range will likely remain similar. The elevational gradient in species richness in the Toiyabe range may flatten, or the patterns in the two ranges may converge.

Measurement of Serum Antigen Concentration by Ultrasound-Enhanced Immunoassay and Correlation with Clinical Outcome in Meningococcal Disease - M. A. Sobanski; R. A. Barnes; S. J. Gray; A. D. Carr; E. B. Kaczmarski; A. O'Rourke; K. Murphy; M. Cafferkey; R. W. Ellis; K. Pidcock; P. Hawtin; W. T. Coakley (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

Soluble organic nitrogen in agricultural soils - D. V. Murphy; A. J. Macdonald; E. A. Stockdale; K. W. T. Goulding; S. Fortune; J. L. Gaunt; P. R. Poulton; J. A. Wakefield; C. P. Webster; W. S. Wilmer (Biology and Fertility of Soils, 2000)

Nanoscale topography of the basement membrane underlying the corneal epithelium of the rhesus macaque - G. A. Abrams; S. L. Goodman; P. F. Nealey; M. Franco; C. J. Murphy (Cell and Tissue Research, 2000)

Combined analysis of field and model data: A case study of the phosphate dynamics in the German Bight in summer 1994 - Th. Pohlmann; Th. Raabe; R. Doerffer; S. Beddig; U. Brockmann; S. Dick; M. Engel; K. -J. Hesse; P. König; B. Mayer; A. Moll; D. Murphy; et al. (Ocean Dynamics, 1999)

SPM concentrations in the German Bight: comparison between a model simulation and measurements - W. Puls; J. Beusekom; U. Brockmann; R. Doerffer; U. Hentschke; P. König; D. Murphy; B. Mayer; A. Müller; Th. Pohlmann; A. Reimer; R. Schmidt-Nia; et al. (Ocean Dynamics, 1999)

Composition and role of tapetal lipid bodies in the biogenesis of the pollen coat of Brassica napus - Inmaculada Hernández-Pinzón; Joanne H. E. Ross; Karen A. Barnes; Andrew P. Damant; Denis J. Murphy (Planta, 1999)

Temporal and spatial gene expression of cytochrome B5 during flower and fruit development in olives - Anna I. Martsinkovskaya; Zaruhi P. Poghosyan; Kosmas Haralampidis; Denis J. Murphy; Polydefkis Hatzopoulos (Plant Molecular Biology, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Interannual variability of the South Georgia marine ecosystem: biological and physical sources of variation in the abundance of krill - E. J. MURPHY; J. L. WATKINS; K. REID; P. N. TRATHAN; I. EVERSON; J. P. CROXALL; J. PRIDDLE; M. A. BRANDON; A. S. BRIERLEY; E. HOFMANN (Fisheries Oceanography, 1998)
Interannual variability is a characteristic feature of the Southern Ocean ecosystem, yet the relative roles of biological and physical processes in generating these fluctuations are unknown. There is now extensive evidence that there are years when there is a very low abundance of Antarctic krill ( Euphausia superba ) in the South Georgia area, and that this variation affects much of the ecosystem, with the most obvious impacts on survival and breeding success of some of the major predators on krill. The open nature of the South Georgia ecosystem means this variability has large‐scale relevance, but even though there are unique time series of data available, information on some key processes is limited. Fluctuations in year‐class success in parts, or all, of the krill population across the Scotia Sea can generate large changes in the available biomass. The ocean transport pathways maintain the large‐scale ecosystem structure by moving krill over large distances to areas where they are available to predator colonies. This large‐scale physical system shows strong spatial and temporal coherence in the patterns of the interannual and subdecadal variability. This physical variability affects both the population dynamics of krill and the transport pathways, emphasizing that both the causes and the consequences of events at South Georgia are part of much larger‐scale processes.

Short-term effects of nitrogen on methane oxidation in soils - P. Tlustos; T. W. Willison; J. C. Baker; D. V. Murphy; D. Pavlikova; K. W. T. Goulding; D. S. Powlson (Biology and Fertility of Soils, 1998)

Genotype/phenotype correlation in affected individuals of a family with a deletion of the entire coding sequence of the connexin 32 gene - P. J. Ainsworth; C. F. Bolton; B. C. Murphy; J. A. Stuart; A. F. Hahn (Human Genetics, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

A mini drivepoint sampler for measuring pore water solute concentrations in the hyporheic zone of sand‐bottom streams - John H. Duff; Fred Murphy; Chrsistopher C. Fuller; Frank J. Triska; Judson W. Harvey; Alan P. Jackman (Limnology and Oceanography, 1998)
A new method for collecting pore‐water samples in gravel streambeds is presented. We developed a mini drivepoint solution sampling (MINIPOINT) technique to collect pore‐water samples at 2.5‐cm vertical resolution. The sampler consisted of six small‐diameter stainless steel drivepoints arranged in a 10‐cm‐diameter circular array. In a simple procedure, the sampler was installed in the streambed to preset drivepoint depths of 2.5, 5.0, 7.5, 10.0, 12.5, and 15.0 cm. Sampler performance was evaluated in the Shingobee River, Minnesota, and Pinal Creek, Arizona, by measuring the vertical gradient of chloride concentration in pore water beneath the streambed that was established by the uninterrupted injection to the stream for 3 d. Pore‐water samples were withdrawn from all drivepoints simultaneously. In the first evaluation, the vertical chloride gradient was unchanged at withdrawal rates between 0.3 and 4.0 ml min − but was disturbed at higher rates. In the second evaluation, up to 70 ml of pore water was withdrawn from each drivepoint at a withdrawal rate of 2.5 ml min −1 without disturbing the vertical chloride gradient. Background concentrations of other solutes were also determined with MINIPOINT sampling. Steep vertical gradients were present for biologically reactive solutes such as DO, NH 4 + , NO 3 − , and dissolved organic C in the top 20 cm of the streambed. These detailed solute profiles in the hyporheic zone could not have been determined without a method for close interval vertical sampling that does not disturb natural logic mixing between stream water and groundwater.

A bioassay to assess the potential effects of sediment resuspension on phytoplankton community composition - Czeslawa Nalewajko; Thomas P. Murphy (Journal of Applied Phycology, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Independent Scientific Review in Natural Resource Management - Gary K. Meffe; P. Dee Boersma; Dennis D. Murphy; Barry R. Noon; H. Ronald Pulliam; Michael E. Soulé; Donald M. Waller (Conservation Biology, 1998)

Gender comparison of peak oxygen uptake: repetitive box lifting versus treadmill running - Bradley C. Nindl; Marilyn A. Sharp; Robert P. Mello; Valerie J. Rice; Michelle M. Murphy; John F. Patton (European Journal of Applied Physiology, 1997)

Evolution of a metamorphic fluid and its role in lode gold mineralisation in the Central lberian Zone - P. J. Murphy; S. Roberts (Mineralium Deposita, 1997)

Regulation of gene expression in the nervous system by reactive oxygen and nitrogen species - Jean E. Merrill; Sean P. Murphy (Metabolic Brain Disease, 1997)

Functional subsensitivity of 5-HT 2A and 5-HT 2C receptors mediating hyperthermia following acute and chronic treatment with 5-HT 2A/2C receptor antagonists - P. Mazzola-Pomietto; Charanjit S. Aulakh; Teresa Tolliver; Dennis L. Murphy (Psychopharmacology, 1997)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Electron microscopic and antigenic studies of uncharacterized viruses. II. Evidence suggesting the placement of viruses in the familyBunyaviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopy and antigenic studies of uncharacterized viruses. I. Evidence suggesting the placement of viruses in familiesArenaviridae, Paramyxoviridae, orPoxviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopic and antigenic studies of uncharacterized viruses. III. Evidence suggesting the placement of viruses in the familyReoviridae - H. G. Zeller; N. Karabatsos; C. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Temperature-sensitive mutants of influenza A virus: Evaluation of the Alaska/77-ts-1 A 2 temperature-sensitive recombinant virus in seronegative adult volunteers - B. R. Murphy; R. M. Chanock; R. G. Douglas; R. F. Betts; D. H. Waterman; H. P. Holley; D. L. Hoover; S. Suwanagool; D. R. Nalin; M. M. Levine (Archives of Virology, 1980)

Viruses isolated from reptiles: Identification of three new members of the familyRhabdoviridae - T. P. Monath; C. B. Cropp; Christina L. Frazier; F. A. Murphy; Sylvia G. Whitfield (Archives of Virology, 1979)

Cold adapted variants of influenza A - S. B. Spring; H. F. Maassab; A. P. Kendal; B. R. Murphy; R. M. Chanock (Archives of Virology, 1977)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

Bovine ephemeral fever virus in cell culture and mice - Frederick A. Murphy; William P. Taylor; Cedric A. Mims; Sylvia G. Whitfield (Archives of Virology, 1972)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

Effect of pentachloronitrobenzene soil treatment on flavor of potatoes - Jennie L. Brogdon; Elsie H. Dawson; A. P. Benson; Elizabeth F. Murphy (American Journal of Potato Research, 1965)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)